Isolating membrane, preparation method thereof, secondary battery, battery module, battery pack and electric device
Patent Information
- Application Number
- CN202280098016.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-11
- Publication Date
- 2025-02-25
AI Technical Summary
In the cell manufacturing process of electrochemical devices, the pole pieces and isolation films are easily misaligned during the transfer process, resulting in reduced dynamic performance and safety performance risks, and it is difficult to achieve appropriate bonding effects under production efficiency requirements with existing technology. At the same time, if the adhesive force of the isolation film is too large or too small during transportation, there will be problems, which will affect subsequent processes.
Provided is an isolation film, which includes a substrate and a coated pressure-sensitive adhesive coating, the coating containing 40-90wt% of first organic particles and 2-15wt% of pressure-sensitive adhesive, and has good Pressure-sensitive properties, with low viscosity at room temperature and high viscosity at high pressure, are suitable for bonding the pole piece to the isolation film, and the surface density and resistance of the coating are within a suitable range to avoid an increase in resistance.
It achieves a tight fit between the electrode piece and the isolation film at room temperature, avoiding misalignment and insufficient bonding, improving the structural stability and safety performance of the battery core, and avoiding excessive bonding during the winding and storage processes to facilitate follow-up. Use, taking into account the cell manufacturing efficiency and dynamic performance.
Smart Images

Figure 00000054_0000 
Figure 00000054_0001 
Figure 00000054_0002
Abstract
Description
Separator, preparation method thereof, secondary battery, battery module, battery pack and electrical device Technical Field
[0001] The present application relates to the field of battery technology, and in particular to an isolation membrane, a preparation method thereof, and a secondary battery, a battery module, a battery pack, and an electrical device comprising the isolation membrane. Background Art
[0002] During the manufacturing process of the battery cells of electrochemical devices, the electrode and the separator will inevitably be misaligned during the transfer process. In the worst case, the electrode will wrinkle after full charging, which will seriously affect the dynamic performance and reduce the safety performance of the battery cell. In the worst case, the electrode will contact each other and cause the dry battery cell to be scrapped. Therefore, technicians will apply an adhesive coating on the separator, and usually pre-press under appropriate pressure in the first composite process of the electrode and the separator of the electrochemical device to ensure that the electrode and the separator of the electrochemical device have a certain degree of adhesion before entering the next process. However, due to the requirements of production efficiency, the pressure and action time in the first process cannot meet the requirements for the electrode and the separator of the electrochemical device to achieve proper adhesion. On the other hand, during the transportation of the separator, there also needs to be proper adhesion between the separators. If the bonding force is too large, it may cause the layers of the separator to stick together, which is not conducive to the subsequent high-speed composite of the electrode and the separator. Therefore, how to ensure proper bonding between the isolation membrane and the electrode to improve safety performance, while at the same time ensuring that the bonding force between the isolation membranes is not too large during transportation, thereby affecting the subsequent use of the isolation membrane, is a difficult problem that technicians urgently need to solve.
[0003] In addition, while solving the above problems, the following issues need to be considered: Will the excessively high surface density of the adhesive worsen the insulation membrane resistance? Is the adhesive strength of the adhesive appropriate at high temperature and room temperature? Will it block the insulation membrane holes and increase the insulation membrane resistance, thereby affecting the dynamic performance of the battery cell?
[0004] It can be seen that it is very meaningful to develop an isolation film that can solve the above problems at the same time.
[0005] Summary of the Invention
[0006] The present application is made in view of the above-mentioned problems, and its purpose is to provide a separator, a preparation method thereof, and a secondary battery, a battery module, a battery pack and an electrical device comprising the separator.
[0007] In order to achieve the above objectives, the first aspect of the present application provides an isolation film, comprising:
[0008] matrix; and
[0009] a coating applied on at least one surface of the substrate, the coating comprising 40-90 wt % of first organic particles, 2-15 wt % of a pressure-sensitive adhesive, and optionally 0-50 wt % of second organic particles;
[0010] wherein the first organic particles include an organic polymer and an inorganic substance, and the pressure-sensitive adhesive includes an organic polymer and a plasticizer;
[0011] Optionally, the volume average particle size of the first organic particles satisfies (Dv90-Dv10) / Dv50≤2.5, optionally ≤2, more optionally ≤1.8, and the glass transition temperature of the first organic particles is 20-100° C., optionally 30-80° C.;
[0012] Optionally, the isolation film meets the requirements of 0.1 g·m -2 Ω -1 ≤ρ / R≤1.0g·m -2 Ω -1 , optional 0.5g·m -2 Ω -1 ≤ρ / R≤0.9g·m -2 Ω -1 , 0.6g·m is more optional -2 Ω -1 ≤ρ / R≤0.8g·m -2 Ω -1 , where ρ represents the surface density of the coating on the substrate, and R represents the resistance of the isolation film at 25°C.
[0013] The isolation film contains a pressure-sensitive adhesive with good pressure-sensitive properties. Its bonding force at ≤1MPa is below 0.08N / m, so it can avoid the isolation film from bonding with the isolation film during the winding and storage process. At the same time, it can have a significant bonding effect with the pole piece at room temperature (usually 20-30℃, such as 25℃) and a pressure of ≥2MPa. Therefore, when using the isolation film to prepare a battery cell, the pole piece and the isolation film can be tightly fitted at room temperature and under appropriate pressure. In addition, optionally, the isolation film meets the requirements of 0.1g·m -2 Ω -1 ≤ρ / R≤1.0g·m -2 Ω -1 , so that the isolation film has excellent bonding performance while not deteriorating the dynamic performance due to the increase in the isolation film resistance.
[0014] In any embodiment, optionally, the first organic particles meet one or more of the following conditions:
[0015] (1) The volume average particle size Dv50 of the first organic particles is 3-36 μm, optionally 5-20 μm;
[0016] (2) The glass transition temperature of the first organic particles is 20-100° C., optionally 30-80° C.;
[0017] (3) The weight average molecular weight of the organic polymer in the first organic particles is 500×10 3 g / mol-1000×10 3 g / mol, optional 800×10 3 g / mol-1000×10 3 g / mol.
[0018] In any embodiment, optionally, the organic polymer in the first organic particles is polymerized from at least the following monomers:
[0019] a first polymerizable monomer having at least one ester bond, which may be selected from one or more of methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, vinyl acetate, trifluoroethyl methacrylate, glycidyl methacrylate, or trimethylolpropane triacrylate, and may further be selected from one or more of methyl methacrylate, lauryl acrylate, lauryl methacrylate, or trimethylolpropane triacrylate;
[0020] The second polymer monomer has at least one cyanide bond, which can be selected from one or more of acrylonitrile, methacrylonitrile, and ethacrylonitrile, and more preferably one or more of acrylonitrile and methacrylonitrile;
[0021] The third polymer monomer has at least one amide bond, and may be one or more of acrylamide, N-hydroxymethyl acrylamide, and N-butoxymethyl acrylamide, and may be one or more of acrylamide and N-hydroxymethyl acrylamide;
[0022] Optionally, the weight ratio of the first polymer monomer: the second polymer monomer: the third polymer monomer is 1: 0-0.8: 0.05-0.75, and optionally 1: 0.1-0.6: 0.1-0.6.
[0023] When the organic polymer is polymerized from the above-mentioned polymer monomers, the first organic particles produced have good bonding properties and a low glass transition temperature. In addition, the spraying surface density ρ of the adhesive material on the isolation film and the resistance R of the isolation film meet 0.1g·m -2 Ω -1 ≤ρ / R≤1.0g·m -2 Ω -1 , which helps to reduce the resistance of the isolation membrane and improve the dynamic performance of the battery using the isolation membrane.
[0024] In any embodiment, optionally, the content of the organic polymer in the first organic particles is 50-99.9%, optionally 60-99%, more optionally 70-99%, based on the total dry weight of the first organic particles;
[0025] The content of inorganic matter in the first organic particles is 0.1-50%, optionally 1-40%, more optionally 1-30%, based on the total dry weight of the first organic particles.
[0026] In any embodiment, optionally, a weight ratio of the organic polymer to the inorganic matter in the first organic particles is from 99:1 to 1:1, optionally from 70:30 to 1:1.
[0027] In any embodiment, optionally, based on the total weight of the organic polymer in the first organic particles,
[0028] The content of the first polymer monomer is 35-80% by weight, optionally 45-70% by weight;
[0029] The content of the second polymerizable monomer is 0-30 wt%, optionally 5-25 wt%; and
[0030] The content of the third polymer monomer is 5-40 wt %, and optionally 8-35 wt %.
[0031] In any embodiment, optionally, the inorganic matter in the first organic particles is selected from one or more of oxides of silicon, aluminum, calcium, zinc, magnesium, and sodium sulfate, sodium benzoate, calcium carbonate and modified materials thereof, and can be selected from one or more of silicon dioxide, silica sol, aluminum oxide, zinc oxide, magnesium oxide, sodium benzoate, and more can be selected from one or more of fumed silica, silicon powder, aluminum oxide, and sodium benzoate.
[0032] In any embodiment, optionally, the surface of the first organic particles is uneven, and inorganic oxide clusters with a particle size of 10-200 nm are evenly distributed.
[0033] In any embodiment, optionally, the mass ratio of the organic polymer to the plasticizer included in the pressure-sensitive adhesive is (4-25):1, optionally (4-11):1.
[0034] The relative contents of the organic polymer and the plasticizer included in the pressure-sensitive adhesive are within the above range, which is conducive to ensuring a greater bonding force between the electrode and the isolation membrane, improving the bonding performance and cycle performance, and at the same time will not cause a significant increase in the resistance of the isolation membrane.
[0035] In any embodiment, optionally, the pressure-sensitive adhesive has a core-shell structure, and the core and shell of the core-shell structure both include an organic polymer and a plasticizer, wherein the mass ratio of the organic polymer to the plasticizer in the core is (3-4):1, optionally (3.2-3.8):1, and the mass ratio of the organic polymer to the plasticizer in the shell structure is (7-9):1, optionally (7.5-8.5):1.
[0036] The core and shell of the core-shell structure are mainly composed of organic polymers and plasticizers, which can further improve the pressure-sensitive properties of the pressure-sensitive adhesive, thereby improving the applicability of the isolation membrane to different pressure conditions, and helping to reduce the resistance of the isolation membrane, thereby improving the dynamic performance of the isolation membrane.
[0037] In any embodiment, optionally, in the pressure sensitive adhesive, a portion of the plasticizer is grafted onto the organic polymer; optionally, in the pressure sensitive adhesive, at least 5 wt % of the plasticizer is grafted onto the organic polymer based on the weight of the plasticizer.
[0038] When a portion of the plasticizer is grafted onto the organic polymer, it can prevent the plasticizer from migrating into the electrolyte in large quantities during the cycle, thereby avoiding the consumption of various functional additives in the electrolyte, which in turn leads to an increase in the resistance of the isolation membrane and affects the dynamic performance of the battery cell.
[0039] In any embodiment, optionally, the pressure-sensitive adhesive has a volume average particle size Dv50 of 0.3-3.5 μm, optionally 0.8-2.0 μm.
[0040] The pressure-sensitive adhesive of appropriate particle size helps to distribute evenly on the first organic particles or both the first organic particles and the second organic particles, helps to bond the core and shell to the pole piece under a certain pressure, and effectively improves the dynamic performance of the isolation membrane.
[0041] In any embodiment, optionally, the pressure-sensitive adhesive has a glass transition temperature of -50°C to 100°C, optionally -45°C to 60°C.
[0042] When the glass transition temperature of the pressure-sensitive adhesive is within the above range, it is beneficial to ensure the bonding strength at room temperature, and avoid the bonding strength being greater than 0.08 N / m at 1 MPa, which causes the isolation film to stick together during storage, making it difficult to reel the isolation film; at the same time, it is avoided that the bonding strength is less than 0.1 N / m at room temperature and 2 MPa, resulting in weak bonding between the isolation film and the electrode, which is not conducive to the shaping of the battery cell.
[0043] In any embodiment, optionally, in the pressure-sensitive adhesive, the organic polymer includes a copolymer formed by copolymerizing a mixture comprising at least one of the following first monomer group, at least one of the second monomer group, at least one of the third monomer group, and at least one of the reactive dispersants:
[0044] The first monomer group includes acrylic acid, methacrylic acid, methyl methacrylate, tert-butyl methacrylate, isobornyl methacrylate, hydroxymethyl acrylamide, acrylamide, styrene, and acrylonitrile;
[0045] The second monomer group: including acrylic acid C4-C 22 Alkyl esters such as isobutyl acrylate, isooctyl acrylate, tert-butyl acrylate, 2-ethylhexyl acrylate (isooctyl acrylate), cyclohexyl acrylate, ethyl methacrylate, isobutyl methacrylate, 2-ethylhexyl methacrylate, n-hexyl methacrylate, cyclohexyl methacrylate, as well as benzyl methacrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, ethyleneureaethyl methacrylate, dicyclopentenylethoxy methacrylate, tetrahydrofuranyl methacrylate, trifluoroethyl methacrylate, dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, propylene methacrylate, dicyclopentenylethoxy methacrylate;
[0046] The third monomer group includes 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, glycidyl acrylate, glycidyl methacrylate, dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriisopropoxysilane, γ-methacryloxypropyltrimethoxysilane, N-hydroxymethyl acrylamide, N-butoxymethyl acrylamide, diacetone acrylamide (DAAM), ethyl acetoacetate methacrylate (AAEM), divinylbenzene, epoxy resin with an epoxy value of 0.35-0.50, and divinylbenzene; and
[0047] Reactive dispersants: including polyvinyl alcohol, polypropylene alcohol, polypropylene glycol, polyethylene glycol, and polyvinyl alcohol.
[0048] In any embodiment, optionally, the alcoholysis degree of the reactive dispersant is ≥85%, and the number average degree of polymerization is 400-2000; preferably, the alcoholysis degree is ≥88%, and the number average degree of polymerization is 500-1600.
[0049] In any embodiment, optionally, the plasticizer is selected from one or more of the following: glycerol C4-C 10 Alkyl diether or monoether, glycerol C4-C 10 Carboxylic acid monoester or diester, propylene glycol C4-C 10 Alkyl monoether or glycerol.
[0050] In any embodiment, optionally, the average thickness of the coating is 0.8-22 μm, optionally 2-15 μm.
[0051] In any embodiment, optionally, the second organic particles are polymers of one or more monomers containing the following groups: halogen, phenyl, epoxy, cyano, ester, and amide;
[0052] Optionally, the second organic particles are selected from at least one of the following: homopolymers or copolymers of fluorine-containing olefinic monomer units, homopolymers or copolymers of olefinic monomer units, homopolymers or copolymers of unsaturated nitrile monomer units, homopolymers or copolymers of alkylene oxide monomer units, dimers, homopolymers or copolymers of monosaccharide monomer units, and modified compounds of the above homopolymers or copolymers.
[0053] In any embodiment, optionally, the fluorine-containing olefinic monomer unit is selected from one or more of difluoroethylene, vinylidene fluoride, trifluoroethylene, chlorotrifluoroethylene, tetrafluoroethylene, hexafluoropropylene or derivatives thereof.
[0054] In any embodiment, optionally, the olefin-based monomer unit is selected from one or more of ethylene, propylene, butadiene, isoprene, styrene or derivatives thereof.
[0055] In any embodiment, optionally, the unsaturated nitrile monomer unit is selected from one or more of acrylonitrile, methacrylonitrile or derivatives thereof.
[0056] In any embodiment, optionally, the alkylene oxide monomer unit is selected from one or more of ethylene oxide, propylene oxide or derivatives thereof.
[0057] In any embodiment, optionally, the monosaccharide monomer unit is selected from glucose or its derivatives.
[0058] In any embodiment, optionally, the second organic particles are selected from at least one of the following: polyperfluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polystyrene-co-methyl methacrylate, polystyrene-co-butyl acrylate, styrene-butyl acrylate-isooctyl acrylate, polymethyl methacrylate, polyacrylonitrile, polyvinyl acetate, polyethylene-co-vinyl acetate, polyimide, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose and cyanoethyl sucrose.
[0059] In any embodiment, optionally, the second organic particles are selected from at least one of the following: polyvinylidene fluoride-co-hexafluoropropylene, polystyrene-co-butyl acrylate, styrene-butyl acrylate-isooctyl acrylate, polyperfluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-co-trichloroethylene.
[0060] In any embodiment, optionally, the second organic particles meet one or more of the following conditions:
[0061] (1) The volume average particle size Dv50 of the second organic particles is 2-20 μm, and can be 6-15 μm;
[0062] (2) The melting point of the second organic particles is 130-160° C., and can be optionally 138-150° C.;
[0063] (3) The weight average molecular weight of the second organic particles is 400×10 3 g / mol-1000×10 3 g / mol, optional 450×10 3 g / mol-650×10 3 g / mol.
[0064] The melting point of the second organic particles is within the above range and can withstand electrolyte swelling. This prevents excessive electrolyte consumption, preventing residual monomers from being bubbled out by the electrolyte and blocking the separator, which could increase separator resistance and affect the battery cell's dynamic performance. Furthermore, the adhesion between the separator and the electrode is not significantly reduced, and the electrode is not easily crushed by the second organic particles, which could compromise safety.
[0065] In any embodiment, optionally, the isolation film satisfies one or more of the following conditions:
[0066] (1) The porosity of the matrix is 10-95%;
[0067] (2) The pore size of the substrate is 20-60 nm;
[0068] (3) The thickness of the substrate is 3-12 μm, optionally 5-9 μm;
[0069] (4) The substrate is a film or nonwoven fabric selected from one or more of the following: polyethylene, polypropylene, polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyaryletherketone, polyetherimide, polyamideimide, polybenzimidazole, polyethersulfone, polyphenylene oxide, cycloolefin copolymer, polyphenylene sulfide and polyethylene naphthalene.
[0070] When the separator satisfies one or more of the above conditions, it is beneficial to further improve the bonding performance of the separator and the dynamic performance and cycle performance of the corresponding secondary battery.
[0071] In any embodiment, optionally, in the isolation film, the mass ratio of the first organic particles to the second organic particles is 10-100:0-90, optionally 20-90:0-60;
[0072] Optionally, the ratio of the sum of the mass of the first organic particles and the second organic particles to the mass of the pressure-sensitive adhesive is 20-92:8-20, or optionally 60-90:10-15.
[0073] The second aspect of the present application provides a method for preparing the isolation film of the first aspect of the present application, which comprises the following steps:
[0074] S1) adding first organic particles and a dispersant to a solvent to form a first polymer solution;
[0075] S2) adding a pressure-sensitive adhesive to the first polymer solution obtained in step S1) and mixing thoroughly to form a second polymer solution;
[0076] S3) optionally, adding second organic particles to the second polymer solution obtained in step S2) and mixing thoroughly to form a third polymer solution; and
[0077] S4) applying the second polymer solution obtained in step S2) or the third polymer solution obtained in step S3) onto at least one surface of the substrate, and drying to obtain a separator;
[0078] The isolation film comprises a substrate and a coating coated on at least one surface of the substrate, wherein the coating comprises 40-90 wt% of first organic particles, 2-15 wt% of a pressure-sensitive adhesive, and optionally 0-50 wt% of second organic particles; wherein the first organic particles comprise an organic polymer and an inorganic substance, and the pressure-sensitive adhesive comprises an organic polymer and a plasticizer; optionally, the volume average particle size of the first organic particles satisfies (Dv90-Dv10) / Dv50≤2.5, optionally ≤2, more optionally ≤1.8, and the glass transition temperature of the first organic particles is 20-100°C, optionally 30-80°C; optionally, the isolation film satisfies 0.1 g·m -2 Ω -1 ≤ρ / R≤1.0g·m -2 Ω -1 , optional 0.5g·m -2 Ω -1 ≤ρ / R≤0.9g·m -2 Ω -1 , 0.6g·m is more optional -2 Ω -1 ≤ρ / R≤0.8g·m -2 Ω -1 , where ρ represents the surface density of the coating on the substrate, and R represents the resistance of the isolation film at 25°C.
[0079] The third aspect of the present application provides a secondary battery, which includes a positive electrode sheet, a negative electrode sheet, an isolation membrane located between the positive electrode sheet and the negative electrode sheet, and an electrolyte, wherein the isolation membrane is the isolation membrane of the first aspect of the present application or an isolation membrane prepared according to the method of the second aspect of the present application.
[0080] In any embodiment, optionally, the bonding force between the positive electrode sheet and the isolation membrane of the secondary battery satisfies 1.2≤F2 / F1≤4, optionally 1.5≤F2 / F1≤3.8, wherein F1 represents the bonding force between the positive electrode sheet and the isolation membrane at 25°C and ≥2MPa, and F2 represents the bonding force between the positive electrode sheet and the isolation membrane at 95°C and ≥2MPa.
[0081] A fourth aspect of the present application provides a battery module, comprising the secondary battery described in the third aspect of the present application. The battery module can be prepared using methods commonly used in the art.
[0082] The fifth aspect of the present application provides a battery pack, comprising at least one of the secondary battery described in the third aspect of the present application or the battery pack described in the fourth aspect of the present application. The battery pack can be prepared using methods commonly used in the art.
[0083] The sixth aspect of the present application provides an electrical device comprising at least one of the secondary battery provided in the third aspect of the present application, the battery module described in the fourth aspect of the present application, or the battery pack described in the fifth aspect of the present application. The electrical device can be manufactured using methods commonly used in the art. Beneficial effects
[0084] The isolation film provided in the present application includes a substrate and a coating coated on at least one surface of the substrate, wherein the coating includes 40-90wt% of a first organic particle, 2-15wt% of a pressure-sensitive adhesive polymer, and optionally 0-50wt% of a second organic particle. The pressure-sensitive adhesive includes an organic polymer and a plasticizer, and the two working together can make the pressure-sensitive adhesive have good pressure-sensitive properties, thereby making the coating have good pressure-sensitive characteristics, and thus making the isolation film also have good pressure-sensitive properties. In particular, the isolation film only has a slight bonding effect with the pole piece at room temperature (usually 20-30°C, for example, 25°C) and a pressure of ≤1MPa, while at room temperature and a pressure of ≥2MPa, the isolation film can have a significant bonding effect with the pole piece, especially at 95°C and a pressure of ≥2MPa, the bonding between the isolation film and the pole piece is significantly improved. This makes it possible to fit the electrode of the electrochemical device tightly to the isolation membrane at room temperature, so as to avoid misalignment between the electrode of the electrochemical device and the isolation membrane during the production transfer process, effectively prevent the wrinkling of the negative electrode caused by insufficient bonding between the isolation membrane and the electrode, and thus ensure the structural stability of the electrochemical device, which is conducive to improving the shell entry rate, thereby improving the shaping performance and safety performance of the battery cell and reducing production costs. On the other hand, the isolation membrane provided in the present application will not be excessively bonded together during the winding and storage process, which is convenient for subsequent use in the preparation of battery cells. In addition, optionally, the volume average particle size of the first organic particles satisfies (Dv90-Dv10) / Dv50≤2.5, and the glass transition temperature is 20℃-100℃, which is conducive to improving the coating condition of the bonding coating, avoiding clogging of the isolation membrane pores, and thus avoiding an increase in the internal resistance of the isolation membrane. Finally, optionally, the isolation membrane described in the present application satisfies 0.1g·m -2 Ω -1 ≤ρ / R≤1.0g·m -2 Ω -1 This helps to ensure that the isolation membrane coating surface density is appropriate, further avoiding excessive isolation membrane resistance, thereby taking into account both the manufacturing efficiency and dynamic performance requirements of the battery cell.
[0085] The battery module, battery pack and electrical device described in the present application include the isolation membrane described in the first aspect of the present application or the secondary battery described in the second aspect of the present application, and thus have the same advantages as the isolation membrane or secondary battery described in the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0086] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following is a brief introduction to the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.
[0087] FIG1 is a schematic diagram of a secondary battery provided in one embodiment of the present application.
[0088] FIG2 is a schematic diagram of a battery module provided in accordance with an embodiment of the present application.
[0089] FIG3 is a schematic diagram of a battery pack provided in accordance with an embodiment of the present application.
[0090] FIG4 is an exploded schematic diagram of FIG3 .
[0091] FIG5 is a schematic diagram of an electrical device provided in one embodiment of the present application.
[0092] FIG6 shows a morphological photograph of the pressure-sensitive coating of the isolation membrane prepared in one embodiment of the present application; FIG6-a, 6-b and 6-c are scanning electron microscope images at different magnifications.
[0093] FIG7 shows a morphological photograph of the pressure-sensitive coating of the isolation membrane prepared in one embodiment of the present application; FIG7 -a, 7 -b and 7 -c are scanning electron microscope images at different magnifications.
[0094] The description of the accompanying drawings is as follows:
[0095] 1. Battery pack; 2. Upper case; 3. Lower case; 4. Battery module; 5. Secondary battery. DETAILED DESCRIPTION
[0096] Below, the embodiments of the isolation membrane, its preparation method, secondary battery, battery module, battery pack and electrical device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0097] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0098] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0099] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0100] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0101] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0102] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0103] In the description of this article, it should be noted that, unless otherwise specified, “above” and “below” are inclusive of the number themselves, and “a variety” in “one or more” means two or more.
[0104] It should be noted that, in this application, the term "average degree of polymerization" refers to a polymer composed of homologous polymer molecules with varying degrees of polymerization, with the degree of polymerization representing a statistical average. There are two most commonly used methods for expressing the average degree of polymerization: the degree of polymerization averaged by the number of molecules is called the number-average degree of polymerization; the degree of polymerization averaged by weight is called the weight-average degree of polymerization. The "average degree of polymerization" referred to in this application refers to the number-average degree of polymerization.
[0105] It should be noted that, in this application, the term "alcoholysis degree" refers to the percentage of hydroxyl groups in the product obtained after alcoholysis to the original groups, and the unit is mole fraction%. For example, if there are 100 original groups (ester groups) and there are 60 hydroxyl groups after alcoholysis, then the alcoholysis degree is 60%.
[0106] It should be noted that, in this application, the terms "primary particles" and "secondary particles" have the meanings commonly used in the art. Specifically, "primary particles" refer to particles that have not formed an agglomerated state, and "secondary particles" refer to particles that are agglomerated by two or more primary particles. Primary particles and secondary particles can be easily distinguished using scanning electron microscopy (SEM) images.
[0107] Secondary batteries have become the preferred power source for electrical devices due to their advantages such as high energy density, portability, no memory effect, and environmental friendliness. The separator in a secondary battery is an important part to ensure the safety performance of the battery. However, on the one hand, during the manufacturing process of the battery cell of the electrochemical device, the electrode and the separator will inevitably be misaligned during the production transfer process. At the very least, the electrode will wrinkle after full charge, seriously affecting the dynamic performance and reducing the safety performance of the battery cell. At the worst, the electrodes will contact each other, causing the dry battery cell to be scrapped. Therefore, technicians will apply an adhesive coating on the separator, and usually pre-press under appropriate pressure in the first composite process of the electrode and the separator of the electrochemical device to ensure that the electrode and the separator of the electrochemical device have a certain degree of adhesion before entering the next process. However, due to the requirements of production efficiency and considering that high pressure will deteriorate the material structure, the pressure and action time in the first process are usually not enough to achieve appropriate bonding between the electrode and the separator of the electrochemical device. In addition, in order to ensure the margin of the battery cell group and the shell insertion rate, it is usually necessary to bake the electrode and the isolation membrane of the electrochemical device in a tunnel oven at 80-100°C for ≥700s, and then apply pressure to make the electrode and the isolation membrane of the electrochemical device fit tightly together. Therefore, if the bonding force between the isolation membrane and the electrode at room temperature (25°C) and the bonding force at high temperature (such as 95°C) do not match well, it may cause insufficient bonding of the battery cell or excessive bonding force, which in turn leads to a significant increase in the resistance of the isolation membrane, deterioration of the battery cell dynamic performance, and even safety risks.
[0108] On the other hand, proper adhesion between separators is also required during transport. Excessive adhesion can cause the separator layers to stick together, hindering the subsequent high-speed assembly of the electrode and separator. Furthermore, the inventors discovered during their research that an inappropriate adhesive material and an inappropriate surface density of the adhesive material can clog the separator pores, resulting in a decrease in the cell's manufacturing yield and reduced dynamic performance.
[0109] To solve the above problems, the inventors found after extensive research that by coating a pressure-sensitive adhesive coating on the isolation membrane substrate, low viscosity at low pressure and high viscosity at high pressure can be achieved. Furthermore, by further regulating the coating density of the pressure-sensitive coating and the resistance of the isolation membrane, the viscosity of the pressure-sensitive coating can be controlled to meet the requirements of 0.1 g·m -2 Ω -1 ≤ρ / R≤1.0g·m -2 Ω -1 , which can further reduce the isolation membrane resistance and improve the dynamic performance of the secondary battery using the isolation membrane.
[0110] Isolation film
[0111] In a first aspect, the present application provides an isolation film, comprising:
[0112] matrix; and
[0113] a coating applied on at least one surface of the substrate, the coating comprising 40-90 wt % of first organic particles, 2-15 wt % of a pressure-sensitive adhesive, and optionally 0-50 wt % of second organic particles;
[0114] wherein the first organic particles include an organic polymer and an inorganic substance, and the pressure-sensitive adhesive includes an organic polymer and a plasticizer;
[0115] Optionally, the volume average particle size of the first organic particles satisfies (Dv90-Dv10) / Dv50≤2.5, optionally ≤2, more optionally ≤1.8, and the glass transition temperature of the first organic particles is 20-100° C., optionally 30-80° C.;
[0116] Optionally, the isolation film meets the requirements of 0.1 g·m -2 Ω -1 ≤ρ / R≤1.0g·m -2 Ω -1 , optional 0.5g·m -2 Ω -1 ≤ρ / R≤0.9g·m -2 Ω -1 , 0.6g·m is more optional -2 Ω -1 ≤ρ / R≤0.8g·m -2 Ω -1 , where ρ represents the surface density of the coating on the substrate, and R represents the resistance of the isolation film at 25°C.
[0117] The present application applies a coating comprising 40-90 wt% of first organic particles, 2-15 wt% of pressure-sensitive adhesive, and optionally 0-50 wt% of second organic particles on at least one surface of a porous isolation membrane substrate. The pressure-sensitive adhesive comprises an adhesive polymer and a plasticizer, which together can make the pressure-sensitive adhesive polymer have good pressure-sensitive properties, thereby making the coating have good pressure-sensitive properties, and further making the isolation membrane also have good pressure-sensitive properties. In particular, the isolation membrane only has a slight bonding effect with the pole piece under a pressure of ≤1 MPa, but can have a significant bonding effect with the pole piece under a pressure of ≥2 MPa. In particular, at 95°C and a pressure of ≥2 MPa, the bonding between the isolation membrane and the pole piece is significantly improved. This makes it possible to fit the electrode of the electrochemical device tightly to the isolation membrane at room temperature, so as to avoid misalignment between the electrode of the electrochemical device and the isolation membrane during the production transfer process, effectively prevent the wrinkling of the negative electrode caused by insufficient bonding between the isolation membrane and the electrode, and thus ensure the structural stability of the electrochemical device, which is conducive to improving the shell entry rate, thereby improving the shaping performance and safety performance of the battery cell and reducing production costs. On the other hand, the isolation membrane provided in the present application will not stick together during the winding and storage process, which is convenient for subsequent use in the preparation of battery cells. In addition, optionally, the volume average particle size of the first organic particles satisfies (Dv90-Dv10) / Dv50≤2.5, and the glass transition temperature is 20℃-100℃, which is conducive to improving the coating condition of the bonding coating and avoiding clogging of the isolation membrane pores. Finally, optionally, the isolation membrane described in the present application satisfies 0.1g·m -2 Ω -1 ≤ρ / R≤1.0g·m -2 Ω -1 This helps to ensure that the isolation film coating surface density is appropriate and further reduce the internal resistance of the isolation film, thereby taking into account the battery cell manufacturing efficiency and dynamic performance requirements.
[0118] In some embodiments, optionally, the weight ratio of the first organic particles: the second organic particles: the pressure-sensitive adhesive on a dry weight basis is 20-90: 0-60: 8-20, optionally 30-80: 30-50: 10-15.
[0119] When the mass ratio of the first organic particles, the second organic particles and the pressure-sensitive adhesive is within the above range, the wettability and distribution uniformity of the electrolyte can be effectively improved, the synergistic advantages of each component can be fully utilized, and the bonding performance, dynamic performance and cycle performance can be improved.
[0120] It should be noted that in this application, the first organic particles are generally designed as primary particles, while the second organic particles are generally designed as secondary particles. Under the combined action of the first organic particles and the second organic particles, the bonding force between the isolation membrane and the electrode plate can be enhanced while further effectively ensuring that the isolation membrane has a moderate and uneven pore structure, which is conducive to ensuring that the coating surface density ρ of the coating on the isolation membrane and the electrical resistance R of the isolation membrane at 25°C meet 0.1g·m -2 Ω -1 ≤ρ / R≤1.0g·m -2 Ω -1 As an example, the ρ / R of the coating is 0.52 g·m -2 Ω -1 , 0.65g·m -2 Ω -1 , 0.8gm -2 Ω -1 , 0.83g·m -2 Ω -1 , 0.9g·m -2 Ω -1 , 0.96g·m -2 Ω -1 or 0.98 g·m -2 Ω -1 and ranges consisting of any two of these.
[0121] It should be noted that in this application, both the first organic particles and the pressure-sensitive adhesive include organic polymers. For ease of distinction, the organic polymer contained in the first organic particles may be referred to as the "first organic polymer," and the organic polymer in the pressure-sensitive adhesive may be referred to as the "third organic polymer."
[0122] In some embodiments, the coating density on the isolation film is optionally 0.1-1.9 g / m 2 , optional 0.25-1.5g / m 2 , and can be selected as 0.65-1.2g / m 2 .
[0123] In addition, during the preparation of the battery cell, the first organic particles are primary particles, which can help form a uniform coating interface and effectively improve the problem of tab misalignment during the preparation of the battery cell.
[0124] [First organic particles]
[0125] In some embodiments, the first organic particles may optionally have a volume average particle size Dv50 of 3-36 μm, optionally 5-20 μm, and for example, 3 μm, 5 μm, 20 μm, 30 μm, or 36 μm, or a range consisting of any two of these.
[0126] When the volume average particle size Dv50 of the first organic particles is within the above range, the first organic particles have a larger average particle size. This can, on the one hand, increase the effective contact area between the electrode and the separator, thereby significantly improving the bonding between the electrode and the separator; on the other hand, it can prevent these organic particles from penetrating into the pores formed in the separator substrate. At the same time, the large size creates relatively large gaps, which can solve the problem of poor air permeability of the separator and reduce the possibility of small particles blocking the separator pores, thereby reducing the risk of increased internal resistance. In addition, because the corners are difficult to composite during the battery cell manufacturing process (especially for prismatic batteries), the separator and the electrode are not bonded here, and the separator cannot effectively transfer the accumulated stress of the electrode to the surrounding area. Moreover, the inherent structural characteristics of the cell module of the prismatic battery can cause the corners to be pushed up, making it difficult to release the stress generated by the expansion of the electrode. Therefore, if there is insufficient space in the battery corners, when the cycle reaches a certain level, that is, when the stress exceeds the elongation of the copper and aluminum foil, the electrode will break, and then puncture the separator, posing a serious safety risk. In this application, the first organic particles have a large average particle size and a certain degree of compression. When they are present at the corners of the battery cell, they can effectively provide stress relief space at the corners. At the same time, the first organic particles satisfy (Dv90-Dv10) / Dv50≤2.5, ensuring that the thickness fluctuation of the isolation film is small. This will not cause an increase in tab misalignment due to the thickness change of the isolation film, which will cause a decrease in the manufacturing quality of the battery cell.
[0127] In some embodiments, the first organic particles may optionally have a glass transition temperature of 20-100° C., or 30-80° C. For example, the glass transition temperature may be 20° C., 30° C., 40° C., 60° C., 80° C., or 100° C., or a range consisting of any two thereof.
[0128] When the glass transition temperature of the first organic particles is within the above range, they can withstand electrolyte swelling. This prevents excessive electrolyte consumption, and residual monomers are less likely to be released by the electrolyte and clog the separator, thereby affecting the battery cell's dynamic performance. Furthermore, the adhesion between the separator and the electrode is not significantly reduced, and the electrode is less likely to be crushed by the first organic particles, thereby reducing safety.
[0129] In some embodiments, optionally, the weight average molecular weight of the organic polymer in the first organic particles is 500×10 3 g / mol-1000×10 3 g / mol, optional 800×103 g / mol-1000×10 3 The weight average molecular weight can be measured by methods commonly used in the art, for example, by gel permeation chromatography according to GB / T 21863-2008.
[0130] In some embodiments, optionally, the first organic particles in the isolation film of the present application comprise an organic polymer and an inorganic substance, wherein the organic polymer in the first organic particles is polymerized from at least the following monomers:
[0131] a first polymerizable monomer having at least one ester bond, which may be selected from one or more of methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, vinyl acetate, trifluoroethyl methacrylate, glycidyl methacrylate, or trimethylolpropane triacrylate, and may further be selected from one or more of methyl methacrylate, lauryl acrylate, lauryl methacrylate, or trimethylolpropane triacrylate;
[0132] The second polymer monomer has at least one cyanide bond, which can be selected from one or more of acrylonitrile, methacrylonitrile, and ethacrylonitrile, and more preferably one or more of acrylonitrile and methacrylonitrile;
[0133] The third polymer monomer has at least one amide bond, and may be one or more of acrylamide, N-hydroxymethyl acrylamide, and N-butoxymethyl acrylamide, and may be one or more of acrylamide and N-hydroxymethyl acrylamide;
[0134] Optionally, the weight ratio of the first polymer monomer: the second polymer monomer: the third polymer monomer is 1: 0-0.8: 0.05-0.75, and optionally 1: 0.1-0.6: 0.1-0.6.
[0135] When the organic polymer is polymerized from the above-mentioned polymer monomers, the first organic particles produced have good bonding properties and a low glass transition temperature. In addition, the spraying surface density ρ of the adhesive material on the isolation film and the resistance R of the isolation film meet 0.1g·m -2 Ω -1 ≤ρ / R≤1.0g·m -2 Ω -1, which helps to reduce the resistance of the isolation membrane and improve the dynamic performance of the battery using the isolation membrane.
[0136] In some embodiments, optionally, the content of the organic polymer in the first organic particles is 50-99.9%, optionally 60-99%, more optionally 70-99%, based on the total dry weight of the first organic particles;
[0137] The content of inorganic matter in the first organic particles is 0.1-50%, optionally 1-40%, more optionally 1-30%, based on the total dry weight of the first organic particles.
[0138] If the first organic particles contain too little organic polymer or too much inorganic material, the first organic particles may have insufficient bonding properties, or even be unable to maintain the organic polymer and inorganic material as a single entity. If the first organic particles contain too little inorganic material, the first organic particles may have poor flame retardancy.
[0139] In some embodiments, optionally, a weight ratio of the organic polymer to the inorganic matter in the first organic particles is 99:1 to 1:1, optionally 70:30 to 1:1.
[0140] When the weight ratio of the organic polymer to the inorganic substance in the first organic particles is within the above range, it is beneficial to give full play to the synergistic function of the organic polymer and the inorganic substance, so that the first organic particles have good bonding properties and flame retardant properties.
[0141] In some embodiments, optionally, based on the total weight of the organic polymer in the first organic particles, the content of the first polymer monomer is 35-80 wt %, optionally 45-70 wt %;
[0142] The content of the second polymerizable monomer is 0-30 wt%, optionally 5-25 wt%; and
[0143] The content of the third polymer monomer is 5-40% by weight, and optionally 8-35% by weight.
[0144] When the contents of the first polymer monomer, the second polymer monomer and the third polymer monomer are all within the above range, it is beneficial to give full play to the synergistic advantages of each monomer, improve the bonding performance of the organic polymer, and at the same time make it have an appropriate glass transition temperature, thereby improving the bonding performance of the first organic particles.
[0145] In some embodiments, optionally, the inorganic matter in the first organic particles is selected from one or more of oxides of silicon, aluminum, calcium, zinc, magnesium, and sodium sulfate, sodium benzoate, calcium carbonate and modified materials thereof, and may be selected from one or more of silicon dioxide, silica sol, aluminum oxide, zinc oxide, magnesium oxide, sodium benzoate, and may be further selected from one or more of fumed silica, silicon powder, aluminum oxide, and sodium benzoate.
[0146] In some embodiments, optionally, the surface of the first organic particles is uneven, and inorganic oxide clusters with a particle size of 10-200 nm are evenly distributed.
[0147] The present application also provides a method for preparing the first organic particles of the present application, comprising at least the following steps:
[0148] Step 1: providing a first polymer monomer, a second polymer monomer and a third polymer monomer, wherein the weight ratio of the first polymer monomer: the second polymer monomer: the third polymer monomer is 1: 0-0.8: 0.05-0.75, and can be optionally 1: 0.1-0.6: 0.1-0.6;
[0149] Step 2: polymerizing the polymer monomer to obtain an organic polymer;
[0150] Step 3: adding an organic solvent and an inorganic substance to the organic polymer of step 2, and stirring to obtain a mixed slurry; and
[0151] Step 4: Dry the mixed slurry from step 3, grind and crush it to obtain the organic first particles described in this application.
[0152] It should be noted that the polymerization of the polymer monomers can be carried out by a polymerization method commonly used in the art, for example, by emulsion polymerization or suspension polymerization.
[0153] In some embodiments, additives such as an emulsifier such as sodium lauryl sulfate and a polymerization initiator such as ammonium persulfate may be optionally added to the polymerization system of the polymer monomer.
[0154] [Pressure-sensitive adhesive]
[0155] The pressure-sensitive adhesive described herein includes an organic polymer and a plasticizer.
[0156] In some embodiments, optionally, the mass ratio of the organic polymer to the plasticizer included in the pressure-sensitive adhesive is (4-25):1, optionally (4-11):1.
[0157] The relative content of the plasticizer included in the pressure-sensitive adhesive is within the above range, which is conducive to ensuring a greater bonding force between the electrode and the isolation membrane, improving the bonding performance and cycle performance, and at the same time will not cause a significant increase in the resistance of the isolation membrane.
[0158] In some embodiments, optionally, the pressure-sensitive adhesive has a core-shell structure, and the core and shell of the core-shell structure both include an organic polymer and a plasticizer, wherein the mass ratio of the organic polymer to the plasticizer in the core is (3-4):1, optionally (3.2-3.8):1, and the mass ratio of the organic polymer to the plasticizer in the shell structure is (7-9):1, optionally (7.5-8.5):1.
[0159] The core and shell of the core-shell structure are both composed of organic polymers and plasticizers, which can further improve the pressure-sensitive properties of the pressure-sensitive adhesive, thereby improving the applicability of the isolation membrane to different pressure conditions, and helping to reduce the resistance of the isolation membrane, thereby improving the dynamic performance of the isolation membrane. On the other hand, the pressure-sensitive adhesive contains a plasticizer. Under a certain pressure (for example, 1-2 MPa), the plasticizer can quickly migrate between the organic polymer and the main material of the isolation membrane, plasticize the adhesive polymer, stretch its molecular chain, and form intermolecular hydrogen bonds with adhesives such as styrene-butadiene rubber (SBR) and thickeners such as sodium carboxymethyl cellulose (CMC) in the negative electrode sheet, and adhesives such as polyvinylidene fluoride (PVDF) in the positive electrode sheet, thereby improving interfacial wetting and enhancing the riveting effect between the two interfaces. Under the action of ≥2 MPa, the core structure is crushed and the plasticizer in the core is released, which can further enhance the above effects.
[0160] In some embodiments, optionally, in the pressure-sensitive adhesive, a portion of the plasticizer is grafted onto the organic polymer; optionally, in the pressure-sensitive adhesive, at least 5 wt% of the plasticizer is grafted onto the organic polymer based on the weight of the plasticizer. As an example, 0 wt%, 3 wt%, 5 wt% or 8 wt% of the plasticizer may be grafted onto the organic polymer, and optionally 8 wt% of the plasticizer is grafted onto the organic polymer.
[0161] When a portion of the plasticizer is grafted onto the organic polymer, it can prevent significant migration of the plasticizer into the electrolyte during cycling, thereby avoiding consumption of various functional additives in the electrolyte, which in turn increases the resistance of the separator and affects the dynamic performance of the battery cell. In particular, when at least 5wt% of the plasticizer is grafted onto the organic polymer backbone, the separator and the electrode can form a "broken lotus root" connection, thereby improving the durability of room-temperature adhesion and reducing rebound. This further ensures that excessive plasticizer does not migrate into the electrolyte during cycling, impacting battery cell performance.
[0162] It should be noted that the grafting rate can be adjusted by methods well known in the art, for example, by adjusting the synthesis time to change the grafting rate. For details, please refer to the patent document with PCT application number PCT / CN2021 / 143069.
[0163] The grafting rate can be tested by a method commonly used in the art, such as infrared testing. As an example, the following steps can be performed: the organic polymer, plasticizer, and pressure-sensitive adhesive are tested to obtain their Fourier infrared spectra, and the pressure-sensitive adhesive has a 1500-1700 cm -1 A peak different from that of the organic polymer and the single plasticizer appears at the position of the peak, which represents the grafted plasticizer. The area under the peak represents the amount of the grafted plasticizer, from which the grafting rate of the plasticizer can be calculated.
[0164] In some embodiments, the pressure-sensitive adhesive may have a volume average particle size Dv50 of 0.3-3.5 μm, or optionally 0.8-2.0 μm, for example, 0.3 μm, 0.5 μm, 0.8 μm, 1.0 μm, 2.0 μm, 3.0 μm, or 3.5 μm, or a range consisting of any two thereof.
[0165] The pressure-sensitive adhesive of appropriate particle size helps to distribute the adhesive evenly on the first or second organic particles, helps to bond the core and shell to the electrode under a certain pressure, and effectively improves the resistance of the isolation film.
[0166] In some embodiments, optionally, the pressure-sensitive adhesive has a glass transition temperature of -50°C to 100°C, optionally -45°C to 60°C.
[0167] When the glass transition temperature of the pressure-sensitive adhesive polymer is within the above range, it is beneficial to ensure the bonding strength at room temperature, avoiding the bonding strength greater than 0.08 N / m at room temperature and 1 MPa, which causes the isolation film to roll up and bond; at the same time, it is avoided that the bonding strength is less than 0.1 N / m at room temperature and 2 MPa, which causes the isolation film and the electrode to have weak bonding, which is not conducive to the shaping of the battery cell.
[0168] In some embodiments, optionally, in the pressure-sensitive adhesive, the organic polymer includes a copolymer formed by copolymerizing a mixture comprising at least one of the following first monomer group, at least one of the second monomer group, at least one of the third monomer group, and at least one of the reactive dispersants:
[0169] The first monomer group: Its melting point is generally higher than 80 ° C, including acrylic acid, methacrylic acid, methyl methacrylate, tert-butyl methacrylate, isobornyl methacrylate, hydroxymethyl acrylamide, acrylamide, styrene, and acrylonitrile;
[0170] The second monomer group: Its melting point is generally not more than 80 ° C, including acrylic acid C4-C 22 Alkyl esters such as isobutyl acrylate, isooctyl acrylate, tert-butyl acrylate, 2-ethylhexyl acrylate (isooctyl acrylate), cyclohexyl acrylate, ethyl methacrylate, isobutyl methacrylate, 2-ethylhexyl methacrylate, n-hexyl methacrylate, cyclohexyl methacrylate, as well as benzyl methacrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, ethyleneureaethyl methacrylate, dicyclopentenylethoxy methacrylate, tetrahydrofuranyl methacrylate, trifluoroethyl methacrylate, dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, propylene methacrylate, dicyclopentenylethoxy methacrylate;
[0171] The third monomer group is a cross-linking monomer containing at least one of a hydroxyl group, an amino group, and a double bond, including 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, glycidyl acrylate, glycidyl methacrylate, dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriisopropoxysilane, γ-methacryloxypropyltrimethoxysilane, N-hydroxymethyl acrylamide, N-butoxymethyl acrylamide, diacetone acrylamide (DAAM), ethyl acetoacetate methacrylate (AAEM), divinylbenzene, an epoxy resin having an epoxy value of 0.35-0.50, and divinylbenzene; and
[0172] Reactive dispersants: including polyvinyl alcohol, polypropylene alcohol, polypropylene glycol, polyethylene glycol, and polyvinyl alcohol.
[0173] In some embodiments, optionally, the mass ratio of the first monomer group monomer: the second monomer group monomer: the third monomer group monomer: the reactive dispersant is 35-45: 45-60: 4-8: 2-5.
[0174] In the present application, the reactive dispersant copolymerizes with the first, second, and third monomers during the synthesis of the pressure-sensitive adhesive to provide a dispersant. Optionally, the reactive dispersant has an alcoholysis degree of 85% or greater and a number-average degree of polymerization of 400-2000; alternatively, the reactive dispersant has an alcoholysis degree of 88% or greater and a number-average degree of polymerization of 500-1600.
[0175] In some embodiments, optionally, the plasticizer is selected from one or more of the following: glycerol C4-C 10 Alkyl diether or monoether, glycerol C4-C 10 Carboxylic acid monoester or diester, propylene glycol C4-C 10 Alkyl monoether or glycerol.
[0176] In some embodiments, optionally, the pressure-sensitive adhesive polymer can be prepared with reference to the patent document with PCT application number PCT / CN2021 / 143069, the entire disclosure of which is incorporated herein by reference.
[0177] In some embodiments, the pressure-sensitive adhesive polymer may be optionally synthesized according to a method comprising the following steps:
[0178] In the first step, an emulsifier and an oligomer are added to a solvent and dispersed uniformly to obtain a first mixed solution;
[0179] The second step is to add a stabilizer to the first mixed solution and disperse it evenly to obtain a second mixed solution;
[0180] Step 3: Add an aqueous initiator to the second mixed solution, mix well, and react at 60-80° C. for 20-60 minutes to obtain a third mixed solution;
[0181] Step 4: uniformly adding the reaction monomer mixture dropwise to the third mixed solution under stirring for 80-100 minutes, for example, 80 minutes, to obtain a fourth mixed solution;
[0182] Step 5: heating the fourth mixed solution to 80-90° C., such as 84° C., and continuously stirring for 120-240 min, such as 180 min, to obtain a fifth mixed solution;
[0183] Step 6: Add a plasticizer to the fifth mixed solution, and react at 80-90° C., such as 84° C., for 120-240 minutes, such as 180 minutes, to obtain a sixth mixed solution;
[0184] Step 7: Add an aqueous initiator to the sixth mixed solution, react at 60-80° C., such as 72° C., for 20-60 min, such as 30 min, to obtain a seventh mixed solution;
[0185] Step 8: uniformly adding the reaction monomer mixture dropwise to the seventh mixed solution under stirring, and obtaining a fourth mixed solution after 100-160 minutes, for example, 120 minutes;
[0186] Step 9: Add a plasticizer to the eighth mixed solution, and react at 80-90° C., such as 84° C., for 120-240 minutes, such as 180 minutes, to obtain a ninth mixed solution;
[0187] Step 10: Cool the ninth mixed solution to below 50° C. and filter to obtain a pressure-sensitive adhesive.
[0188] In some embodiments, optionally, the solvent used in the first step is deionized water.
[0189] In some embodiments, optionally, in the first step, 0.1-1 wt % of an emulsifier and 2-3 wt % of an oligomer are added sequentially, based on the total weight of the reactive monomer mixture (comprising monomers of the first monomer group, monomers of the second monomer group, monomers of the third monomer group, and a reactive dispersant), auxiliary agents (including emulsifiers, stabilizers, and aqueous initiators), and plasticizers added when synthesizing the pressure-sensitive adhesive, the same below.
[0190] In some embodiments, optionally, the emulsifier is selected from one or more of allyl sulfonate, polyoxyethylene alkyl ether, polyoxyethylene aryl ether, and sorbitol.
[0191] In some embodiments, optionally, the stabilizer is selected from one or more of polyethylene oxide, allyl polyether sulfate, methylene succinic acid (itaconic acid), styrene sulfonic acid, sodium vinyl sulfonate, and sodium nanocellulose.
[0192] In some embodiments, optionally, the aqueous initiator is selected from one or more of sodium bicarbonate, benzoyl peroxide, lauroyl peroxide, isopropyl benzene hydroperoxide, tert-butyl hydroperoxide, di-tert-butyl peroxide, diisopropyl benzene peroxide, tert-butyl peroxybenzoate, tert-butyl peroxyvalerate, methyl ethyl ketone peroxide, cyclohexanone peroxide, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, potassium persulfate, sodium persulfate, ammonium persulfate, azobisisobutyronitrile, azobisisoheptylonitrile, and ammonium persulfate-sodium bicarbonate.
[0193] In some embodiments, optionally, the oligomer has a number average molecular weight of ≤1000 and a melting point of 0-30°C.
[0194] In some embodiments, optionally, the oligomer is selected from, for example, octadecyl methacrylate.
[0195] In some embodiments, optionally, in the first step, uniform dispersion is achieved by dispersing at a rotation speed of 8000-12000 r / min (revolutions per minute), such as 10000 r / min, for 20-60 min, such as 50 min.
[0196] In some embodiments, optionally, the operating temperature in the first step is 20-40°C, such as 25°C.
[0197] In some embodiments, optionally, 1-4 wt % of a stabilizer is added to the first mixed solution in the second step.
[0198] In some embodiments, optionally, in the second step, uniform mixing is achieved by mixing at 6000-8000 r / min, such as 6500 r / min, for 20-60 min, such as 30 min.
[0199] In some embodiments, optionally, the operating temperature in the second step is 20-60°C, such as 45°C.
[0200] In some embodiments, optionally, 0.05-0.5 wt % of an aqueous initiator is added to the second mixed solution in the third step.
[0201] In some embodiments, optionally, in the third step, uniform mixing is achieved by mixing at 8000-12000 r / min, such as 8000 r / min, for 20-60 min, such as 30 min.
[0202] In some embodiments, optionally, the operating temperature in the third step is 60-80°C, such as 72°C.
[0203] In some embodiments, optionally, in the fourth step, 35% to 45% by weight of the reaction monomer mixture is added dropwise to the third mixed solution.
[0204] In some embodiments, optionally, the stirring speed in the fourth step is 100-1000 r / min, such as 400 r / min.
[0205] In some embodiments, optionally, the dripping in the fourth step is preferably completed within 60 minutes.
[0206] In some embodiments, optionally, the stirring speed in the fifth step is 12000-18000 r / min, such as 15000 r / min.
[0207] In some embodiments, optionally, 10-20 wt % of a plasticizer such as glycerol is added to the fifth mixed solution in the sixth step.
[0208] In some embodiments, optionally, the stirring speed in the sixth step is 12000-18000 r / min, such as 15000 r / min.
[0209] In some embodiments, optionally, 0.05-0.5% by weight of an aqueous initiator is added to the sixth mixed solution in the seventh step.
[0210] In some embodiments, optionally, the stirring speed in the seventh step is 8000-12000 r / min, such as 8000 r / min.
[0211] In some embodiments, optionally, in the eighth step, 30% to 40% by weight of the reaction monomer mixture is added dropwise to the seventh mixed solution.
[0212] In some embodiments, optionally, the stirring speed in the eighth step is 100-1000 r / min, such as 400 r / min.
[0213] In some embodiments, optionally, in the eighth step, the reaction monomer mixture can be added just within 60 minutes.
[0214] In some embodiments, optionally, 5-20 wt % of a plasticizer such as glycerol is added to the eighth mixed solution in the ninth step.
[0215] In some embodiments, optionally, the stirring speed in the ninth step is 12000-18000 r / min, such as 15000 r / min.
[0216] It should be noted that those skilled in the art can also refer to the above method (omitting steps 7 to 9 and changing the mass fractions of the added plasticizer and the reaction monomer mixture accordingly) to synthesize a non-core-shell pressure-sensitive adhesive polymer.
[0217] [Second organic particles]
[0218] The coating layer of the isolation film described in the present application may optionally further include second organic particles.
[0219] In some embodiments, the second organic particles are optionally polymers of one or more monomers containing the following groups: halogen, phenyl, epoxy, cyano, ester, and amide.
[0220] In some embodiments, optionally, the second organic particles are selected from at least one of the following: homopolymers or copolymers of fluorine-containing olefinic monomer units, homopolymers or copolymers of olefinic monomer units, homopolymers or copolymers of unsaturated nitrile monomer units, homopolymers or copolymers of alkylene oxide monomer units, dimers, homopolymers or copolymers of monosaccharide monomer units, and modified compounds of the above homopolymers or copolymers.
[0221] In some embodiments, the fluorine-containing olefinic monomer unit is selected from one or more of difluoroethylene, vinylidene fluoride, trifluoroethylene, chlorotrifluoroethylene, tetrafluoroethylene, hexafluoropropylene, or derivatives thereof.
[0222] In some embodiments, the olefin-based monomer unit is selected from one or more of ethylene, propylene, butadiene, isoprene, styrene, or derivatives thereof.
[0223] In some embodiments, the unsaturated nitrile monomer unit is selected from one or more of acrylonitrile, methacrylonitrile or derivatives thereof.
[0224] In some embodiments, the alkylene oxide monomer unit is selected from one or more of ethylene oxide, propylene oxide or derivatives thereof.
[0225] In some embodiments, the monosaccharide monomer unit is selected from glucose or its derivatives.
[0226] In some embodiments, the second organic particles are selected from at least one of the following: polyperfluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polystyrene-co-methyl methacrylate, polystyrene-co-butyl acrylate, styrene-butyl acrylate-isooctyl acrylate, polymethyl methacrylate, polyacrylonitrile, polyvinyl acetate, polyethylene-co-vinyl acetate, polyimide, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose and cyanoethyl sucrose.
[0227] In some embodiments, the second organic particles may be at least one selected from the group consisting of polyvinylidene fluoride-co-hexafluoropropylene, polystyrene-co-butyl acrylate, styrene-butyl acrylate-isooctyl acrylate, polyperfluoroethylene, polyvinylidene fluoride, and polyvinylidene fluoride-co-trichloroethylene.
[0228] The second organic particles can be prepared similarly to the first organic particles by a polymerization method commonly used in the art, such as emulsion polymerization or suspension polymerization.
[0229] In some embodiments, the second organic particles meet one or more of the following conditions:
[0230] (1) The volume average particle size Dv50 of the second organic particles is 2-20 μm, and can be 6-15 μm;
[0231] (2) The melting point of the second organic particles is 130-160° C., and can be optionally 138-150° C.;
[0232] (3) The weight average molecular weight of the second organic particles is 400×10 3 g / mol-1000×10 3 g / mol, optional 450×10 3 g / mol-650×10 3 g / mol.
[0233] Using second organic particles within the above particle size range allows for the formation of ample, unevenly distributed gaps between the first and second organic particles during normal secondary battery operation, ensuring smooth ion transport channels and thus enhancing battery cycle performance. The combined action of the first and second organic particles enhances the adhesion between the separator and the electrode while effectively ensuring a moderately uneven pore structure within the separator.
[0234] The melting point of the second organic particles is within the above range and can withstand electrolyte swelling. This prevents excessive electrolyte consumption and prevents residual monomers from being released by the electrolyte and blocking the separator, thereby affecting the battery cell's dynamic performance. Furthermore, the adhesion between the separator and the electrode is not significantly reduced, and the electrode is not easily crushed by the second organic particles, thereby reducing safety.
[0235] As an example, the volume average particle size Dv50 of the second organic particles may be 2 μm, 8 μm, 10 μm, or 12 μm.
[0236] In some embodiments, the isolation film satisfies one or more of the following conditions:
[0237] (1) The porosity of the matrix is 10-95%;
[0238] (2) The pore size of the substrate is 20-60 nm;
[0239] (3) The thickness of the substrate is 3-12 μm, optionally 5-9 μm;
[0240] (4) The substrate is a film or nonwoven fabric selected from one or more of the following: polyethylene, polypropylene, polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyaryletherketone, polyetherimide, polyamideimide, polybenzimidazole, polyethersulfone, polyphenylene oxide, cycloolefin copolymer, polyphenylene sulfide and polyethylene naphthalene.
[0241] When the separator satisfies one or more of the above conditions, it is beneficial to further improve the bonding performance of the separator and the dynamic performance and cycle performance of the corresponding secondary battery.
[0242] In some embodiments, optionally, in the isolation film, the mass ratio of the first organic particles to the second organic particles is 10-100:0-90, optionally 20-90:0-60;
[0243] Optionally, the ratio of the sum of the mass of the first organic particles and the second organic particles to the mass of the pressure-sensitive adhesive is 20-92:8-20, or optionally 60-90:10-15.
[0244] As an example, the mass ratio of the first organic particles to the second organic particles may be 100:0, 90:10, 70:30, 50:50, 40:60, 65:25, or 75:10, or a range consisting of any two of these ratios.
[0245] As an example, the ratio of the sum of the mass of the first organic particles and the second organic particles to the mass of the pressure-sensitive adhesive may be 60:10, 80:10, 85:15, 90:10, or 110:10, or a range consisting of any two of these ratios.
[0246] In some embodiments, the coating has an average thickness of 0.8-22 μm, optionally 2-15 μm. For example, the average thickness can be 0.8 μm, 2 μm, 3 μm, 4 μm, 6 μm, 10 μm, 12 μm, 15 μm, 20 μm, or 22 μm, or a range consisting of any two thereof.
[0247] Preparation method of isolation film
[0248] The second aspect of the present application provides a method for preparing the isolation film according to the first aspect of the present application, which comprises the following steps:
[0249] S1) adding first organic particles and a dispersant to a solvent to form a first polymer solution;
[0250] S2) adding a pressure-sensitive adhesive to the first polymer solution obtained in step S1) and mixing thoroughly to form a second polymer solution;
[0251] S3) optionally, adding second organic particles to the second polymer solution obtained in step S2) and mixing thoroughly to form a third polymer solution; and
[0252] S4) coating the second polymer solution obtained in step S2) or the third polymer solution obtained in step S3) onto at least one surface of the substrate, and drying to obtain a separator;
[0253] The isolation film comprises a substrate and a coating coated on at least one surface of the substrate, wherein the coating comprises 40-90 wt% of first organic particles, 2-15 wt% of a pressure-sensitive adhesive, and optionally 0-50 wt% of second organic particles; wherein the first organic particles comprise an organic polymer and an inorganic substance, and the pressure-sensitive adhesive comprises an organic polymer and a plasticizer; optionally, the volume average particle size of the first organic particles satisfies (Dv90-Dv10) / Dv50≤2.5, optionally ≤2, more optionally ≤1.8, and the glass transition temperature of the first organic particles is 20-100°C, optionally 30-80°C; optionally, the isolation film satisfies 0.1 g·m -2 Ω -1 ≤ρ / R≤1.0g·m -2 Ω -1 , optional 0.5g·m -2 Ω -1 ≤ρ / R≤0.9g·m -2 Ω -1 , 0.6g·m is more optional -2 Ω -1 ≤ρ / R≤0.8g·m -2 Ω -1 , where ρ represents the surface density of the coating on the substrate, and R represents the resistance of the isolation film at 25°C.
[0254] In some embodiments, non-limiting examples of the dispersant used in step S1) may include acrylate (such as BYK brand 22136), branched alcohol polyether (such as Dow brand TMN-6), polyethylene glycol trimethyl nonyl ether, or mixtures thereof.
[0255] In some embodiments, non-limiting examples of the solvent used in step S1) may include acetone, tetrahydrofuran, dichloromethane, chloroform, dimethylformamide, N-methyl-2-pyrrolidone, cyclohexane, water, or a mixture thereof.
[0256] In some embodiments, non-limiting examples of the coating method used in step S4) may include dip coating, die coating, roller coating, comma coating, spin coating, or a combination thereof. The double-sided coating surface density after drying may be 0.32-1.92 g / m 2 .
[0257] [Secondary battery]
[0258] A third aspect of the present application provides a secondary battery having good safety performance and dynamic performance.
[0259] Typically, a secondary battery consists of a positive electrode, a negative electrode, an electrolyte, and a separator. During charging, active ions are inserted and removed between the positive and negative electrodes. The electrolyte conducts ions between the positive and negative electrodes. Secondary batteries using electrolytes, as well as some using semi-solid electrolytes, also include a separator. This separator is placed between the positive and negative electrodes, primarily to prevent short circuits between the positive and negative electrodes while allowing ions to pass through.
[0260] In the secondary battery provided in the present application, the isolation membrane can use the isolation membrane provided in the first aspect of the present application. The isolation membrane has good ion conductivity and adhesion performance at room temperature. Its resistance at room temperature (usually 20-30°C, for example, 25°C) is below 1.6Ω, especially below 1.2Ω; the adhesion force under ≤1MPa is below 0.1N / m, especially below 0.08N / m; the adhesion force with the electrode at ≥2Mpa and room temperature is above 0.15N / m, especially above 0.4N / m; at ≥2MPa and 95°C, the adhesion force with the electrode is below 4.9N / m, especially below 1.8N / m.
[0261] When a secondary battery is prepared using the separator provided by the first aspect of the present application, the bonding force F1 between the positive electrode sheet and the separator at room temperature of 25°C and ≥2MPa and the bonding force F2 between the positive electrode sheet and the separator at 95°C and ≥2MPa satisfy 1.2≤F2 / F1≤4, and optionally 1.5≤F2 / F1≤3.8. At the same time, the density ρ of the coating on the substrate and the resistance R of the separator at 25°C satisfy 0.1g·m -2 Ω -1 ≤ρ / R≤1.0g·m -2 Ω -1 , optional 0.5g·m -2 Ω -1 ≤ρ / R≤0.9g·m -2 Ω -1 , 0.6g·m is more optional -2 Ω -1 ≤ρ / R≤0.8g·m -2 Ω -1When F2 / F1 is greater than 4, the pre-cooling pressure during the cell winding process is insufficient, which may cause the cell to become fluffy, the separator and the electrode to be misaligned, or even the inner electrode to sag, posing a safety risk of overlapping and short-circuiting the electrode. At the same time, improper hot pressing and bonding may make it difficult for the electrolyte to penetrate, affecting the cell's formation efficiency. This can lead to the formation of black spots and even lithium deposition after full charge, seriously affecting the cell's dynamics and safety performance. When F2 / F1 is less than 1.2, although the pre-cooling pressure meets the process requirements, the cell thickness and width may exceed the specifications and become fluffy during the hot pressing process in the tunnel furnace, or the cell may become fluffy after standing for a period of time, which may lead to a decrease in cell yield and production efficiency. In addition, the greater risk is that after the cell is placed in the shell and the electrolyte is injected, the cell hardness will drop significantly, which may cause the electrode to separate from the separator and increase the expansion force of the cell. Even more seriously, if the adhesion between the separator and the electrode is too low, it may not be able to restrain the rebound of the negative electrode, causing wrinkling, triggering lithium deposition problems, and deteriorating the cell's cycle performance.
[0262] [Positive electrode]
[0263] The positive electrode sheet includes a positive electrode current collector and a positive electrode membrane disposed on at least one surface of the positive electrode current collector and including a positive electrode active material. For example, the positive electrode current collector has two opposing surfaces in its thickness direction, and the positive electrode membrane is disposed on either or both of the two opposing surfaces of the positive electrode current collector.
[0264] The positive electrode current collector can be made of a material with good electrical conductivity and mechanical strength. In some embodiments, the positive electrode current collector can be made of aluminum foil.
[0265] The present application does not impose any specific restrictions on the specific type of positive electrode active material. Materials known in the art that can be used for secondary battery positive electrodes can be used, and those skilled in the art can make the selection based on actual needs.
[0266] In some embodiments, the secondary battery provided in the present application is a lithium-ion secondary battery. The positive electrode active material includes a positive electrode active material for a lithium-ion secondary battery that is well known in the art. For example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM333 ), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 ), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 ), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 ), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds. Examples of olivine-structured lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0267] In some embodiments, optionally, the mass percentage of the positive electrode active material in the positive electrode film is 75% to 99%, optionally 80% to 97%.
[0268] In some embodiments, the positive electrode membrane may optionally include a binder. The type of binder is not particularly limited, and those skilled in the art may select the binder based on actual needs. For example, the binder for the positive electrode membrane may include one or more of polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE).
[0269] In some embodiments, optionally, the binder accounts for 0.1% to 3.5% by mass of the positive electrode membrane, optionally 0.5% to 3% by mass.
[0270] In some embodiments, the positive electrode membrane may optionally include a conductive agent. The type of conductive agent is not specifically limited, and those skilled in the art may select the conductive agent based on actual needs. For example, the conductive agent used in the positive electrode membrane may include one or more of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0271] In some embodiments, optionally, the conductive agent accounts for 0.05% to 5% by mass of the positive electrode film, optionally 0.5% to 3% by mass.
[0272] In some embodiments, the step of preparing a positive electrode sheet using a positive electrode active material may include: dispersing the positive electrode active material, a binder, and an optional conductive agent in a solvent, which may be N-methylpyrrolidone, and stirring evenly under the action of a vacuum mixer to obtain a positive electrode slurry; uniformly coating the positive electrode slurry on a positive electrode current collector aluminum foil, drying it at room temperature, and then transferring it to an oven for drying, and then cold pressing and cutting it to obtain a positive electrode sheet.
[0273] [Negative electrode]
[0274] The negative electrode sheet includes a negative electrode current collector and a negative electrode film disposed on at least one surface of the negative electrode current collector. As an example, the negative electrode current collector has two surfaces that are opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposing surfaces of the negative electrode current collector.
[0275] The negative electrode current collector can be made of a material with good electrical conductivity and mechanical strength to perform both electrical conduction and current collection. In some embodiments, the negative electrode current collector can be made of copper foil.
[0276] The negative electrode membrane includes a negative electrode active material. The steps of preparing a negative electrode sheet using the negative electrode active material may include: dispersing the negative electrode active material, a binder, and an optional thickener and a conductive agent in a solvent, the solvent may be deionized water, to form a uniform negative electrode slurry; coating the negative electrode slurry on the negative electrode collector, and obtaining a negative electrode sheet after drying, cold pressing and other processes.
[0277] In some embodiments, the present application does not impose any specific restrictions on the type of negative electrode active material. The negative electrode plate may optionally include any negative electrode active material that can be used in a negative electrode of a secondary battery. The negative electrode active material may be one or more of graphite materials (e.g., artificial graphite, natural graphite), mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon-based materials, and tin-based materials.
[0278] In some embodiments, optionally, the mass percentage of the negative electrode active material in the positive electrode membrane is 75% to 99%, optionally 80% to 97%.
[0279] In some embodiments, the adhesive can be selected from one or more of polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0280] In some embodiments, optionally, the binder accounts for 0.1% to 3.5% by mass of the negative electrode film, optionally 0.5% to 2.5% by mass.
[0281] In some embodiments, the thickening agent may be sodium carboxymethylcellulose (CMC-Na).
[0282] In some embodiments, optionally, the mass percentage of the thickener in the negative electrode membrane is 0.04% to 5%, optionally 0.5% to 3%.
[0283] In some embodiments, the conductive agent used for the negative electrode sheet may be selected from one or more of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0284] In some embodiments, optionally, the conductive agent accounts for 0.04% to 5% by mass of the negative electrode membrane, optionally 0.5% to 3% by mass.
[0285] [Electrolytes]
[0286] The electrolyte conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.
[0287] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0288] In some embodiments, the electrolyte salt may be selected from one or more of LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiAsF6 (lithium hexafluoroarsenate), LiFSI (lithium bisfluorosulfonyl imide), LiTFSI (lithium bistrifluoromethanesulfonyl imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluorooxalatoborate), LiBOB (lithium dioxalatoborate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluorooxalatophosphate), and LiTFOP (lithium tetrafluorooxalatophosphate).
[0289] In some embodiments, the concentration of the electrolyte salt in the non-aqueous electrolyte is, for example, 0.3 mol / L (mole / liter) or higher, optionally 0.7 mol / L or higher, optionally 1.7 mol / L or lower, and further optionally 1.2 mol / L or lower.
[0290] In some embodiments, the solvent can be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0291] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, or additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, and additives that improve battery low-temperature performance.
[0292] [Outer packaging]
[0293] In some embodiments, a secondary battery may include an outer packaging for encapsulating a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte. For example, the positive electrode sheet, the negative electrode sheet, and the separator may be stacked or wound to form a laminated or wound cell structure, which is encapsulated within the outer packaging. The electrolyte may be a liquid electrolyte, which is impregnated within the cell. The number of cells in a secondary battery may be one or more, and can be adjusted based on demand.
[0294] In some embodiments, the outer packaging of the secondary battery may be a soft bag, such as a pouch-type soft bag. The soft bag may be made of plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS). The outer packaging of the secondary battery may also be a hard shell, such as an aluminum shell.
[0295] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.
[0296] The present application has no particular limitation on the shape of the secondary battery, which can be cylindrical, square, or any other shape. FIG1 shows a secondary battery 5 with a square structure as an example.
[0297] [Battery modules, battery packs, and power-consuming devices]
[0298] A fourth aspect of the present application provides a battery module, comprising the secondary battery described in the third aspect of the present application.
[0299] In some embodiments, the secondary batteries provided in this application can be assembled into a battery module. The battery module can contain multiple secondary batteries, and the specific number can be adjusted according to the application and capacity of the battery module.
[0300] Figure 2 shows an example battery module 4. Referring to Figure 2 , within the battery module 4, multiple secondary batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple secondary batteries 5 may be secured using fasteners.
[0301] Optionally, the battery module 4 may further include a housing having an accommodation space, and the plurality of secondary batteries 5 are accommodated in the accommodation space.
[0302] A fifth aspect of the present application provides a battery pack comprising at least one of the secondary battery described in the third aspect of the present application or the battery module described in the fourth aspect of the present application.
[0303] In some embodiments, battery modules assembled from secondary batteries may be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0304] Figures 3 and 4 illustrate an example battery pack 1. Referring to Figures 3 and 4 , the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 can be placed over the lower case 3 to form an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0305] A sixth aspect of the present application provides an electrical device comprising at least one of the secondary battery provided in the third aspect of the present application, the battery module provided in the fourth aspect of the present application, or the battery pack provided in the fifth aspect of the present application, to provide power for the electrical device. The electrical device may be, but is not limited to, a mobile device (e.g., a mobile phone, a laptop computer, etc.), an electric vehicle (e.g., a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship, a satellite, an energy storage system, etc.
[0306] The electrical device may select a secondary battery, a battery module or a battery pack according to its usage requirements.
[0307] Figure 5 shows an example of an electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.
[0308] As another example, the electric device may be a mobile phone, a tablet computer, a laptop computer, etc. Such an electric device is usually required to be lightweight and thin, and may use a secondary battery as a power source.
[0309] Example
[0310] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0311] Example 1
[0312] Preparation of first organic particles (P1)
[0313] At room temperature, the required monomers were uniformly mixed in a weight ratio of 25% 2-hydroxyethyl acrylate, 20% n-butyl acrylate, 5% methyl methacrylate, 5% trimethylolpropane triacrylate, 20% acrylonitrile, and 25% acrylamide. To a 10L four-necked flask equipped with a mechanical stirrer, a thermometer, and a condenser tube, 2kg of the mixed monomers, 60g of sodium lauryl sulfate emulsifier, 20g of ammonium persulfate initiator, and 2.40kg of deionized water were added. The mixture was stirred and emulsified at 1600 rpm for 30 minutes. The mixture was then heated to 75°C under nitrogen and allowed to react for 4 hours. The pH was then adjusted to 6.5 using a 1wt% aqueous solution of NaOH. The mixture was immediately cooled to below 40°C and discharged to yield an organic polymer emulsion with a solids content of approximately 45%.
[0314] The above organic polymer and silicon dioxide were added to an appropriate amount of deionized water at a dry weight ratio of 9:1, stirred for 1 hour to fully mix, and then spray-dried to remove the solvent to obtain a powder. The powder was then ground and pulverized to obtain a Dv50 particle size of 8 μm, a particle size distribution of (Dv90-Dv10) / Dv50 of 1.76, a DSC glass transition temperature of 60°C, and a weight-average molecular weight of approximately 600×10 3 g / mol of the first organic particles.
[0315] Preparation of pressure-sensitive adhesives
[0316] The pressure-sensitive adhesive includes an organic polymer and a plasticizer. The organic polymer is a copolymer of 30 wt% isobutyl acrylate, 25 wt% isooctyl acrylate, 5 wt% 2-hydroxypropyl methacrylate, 15 wt% styrene, 22 wt% acrylonitrile, and 3 wt% polyvinyl alcohol. The plasticizer is glycerol, with a grafting ratio of 8 wt%. The preparation method can be referenced to PCT application number PCT / CN2021 / 143069.
[0317] Preparation of isolation membrane
[0318] 1) A polyethylene microporous membrane (purchased from Shanghai Enjie Co., Ltd.) with a thickness of approximately 9 μm, a pore size of approximately 50 nm, and a porosity of approximately 38% was used as the separator substrate;
[0319] 2) adding 3.3 kg of a pressure-sensitive adhesive (having a glass transition temperature of approximately 10° C. and a volume average particle size Dv50 of approximately 1.1 μm, comprising an organic polymer and a plasticizer in a mass ratio of 5:1 (wherein approximately 8 wt % of the plasticizer is grafted onto the organic polymer relative to the weight of the plasticizer), wherein the organic polymer is a copolymer of 30 wt % isobutyl acrylate, 25 wt % isooctyl acrylate, 5 wt % 2-hydroxypropyl methacrylate, 15 wt % styrene, 22 wt % acrylonitrile, and 3 wt % polyvinyl alcohol, and the plasticizer is glycerol) to 23.6 kg of deionized water to obtain a first polymer solution;
[0320] 3) An appropriate amount of first organic particles (P1, 25 wt% 2-hydroxyethyl acrylate + 20 wt% n-butyl acrylate + 5 wt% methyl methacrylate + 5 wt% trimethylolpropane triacrylate + 20 wt% acrylonitrile + 25 wt% acrylamide, Dv50 particle size of 6 μm, (Dv90-Dv10) / Dv50 of 1.76, glass transition temperature of 60°C, and weight average molecular weight of about 600×10 3 g / mol) and 18 g of a dispersant (BYK-22136, BYK Chemical, brand 22136) were added to the first polymer solution obtained in step 2), and the mixture was thoroughly mixed to form a second polymer solution, wherein the mass ratio of the first organic particles to the pressure-sensitive adhesive in the second polymer solution on a dry weight basis was 90:10;
[0321] 4) The second polymer solution obtained in step 3) was used as an aqueous coating slurry and coated on both surfaces of the isolation film substrate by spin spraying. After drying, 32 locations were taken, and the weight change of the isolation film before and after spin spraying per unit area at each location was calculated. The average value was taken to obtain the surface density ρ of the isolation film coating of 0.97 g / m 2The prepared isolation film includes an isolation film substrate and a pressure-sensitive coating coated on both surfaces of the isolation film substrate. The pressure-sensitive coating has a thickness of about 3 μm and includes first organic particles and a pressure-sensitive adhesive in a mass ratio of 90:10 on a dry weight basis. The pressure-sensitive adhesive includes an organic polymer and a plasticizer in a mass ratio of 5:1 (wherein about 8 wt% of the plasticizer is grafted onto the organic polymer relative to the weight of the plasticizer).
[0322] Preparation of secondary batteries
[0323] The active material LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2, conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF, weight-average molecular weight 1.2 million g / mol) were thoroughly stirred and mixed in a solvent of N-methylpyrrolidone at a weight ratio of 94:3:3 to obtain a positive electrode slurry. The slurry was coated on aluminum (Al) foil, dried, and cold-pressed to obtain a positive electrode sheet. The positive electrode active material loading on the positive electrode sheet was 0.32g / 1540.25mm 2 , density is 3.45g / cm 3 .
[0324] Active material artificial graphite, conductive agent acetylene black, binder styrene butadiene rubber (SBR), thickener sodium carbon methyl cellulose (CMC) were mixed thoroughly in deionized water at a weight ratio of 95:2:2:1 to obtain a negative electrode slurry. The slurry was coated on copper (Cu) foil, dried, and cold pressed to obtain a negative electrode sheet. The graphite loading on the negative electrode sheet was 0.18g / 1540.25mm 2 , density is 1.65g / cm 3 .
[0325] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 3:5:2, and then LiPF6 was uniformly dissolved in the above solution to obtain an electrolyte solution. The concentration of LiPF6 in the electrolyte solution was 1 mol / L.
[0326] The separators prepared in the examples or comparative examples were used as separators for secondary batteries.
[0327] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator positioned between the positive and negative electrodes to provide isolation. The cells are then wound to form a bare cell. The bare cell is placed in an outer packaging, injected with electrolyte, and packaged to form a secondary battery. It should be noted that if the separator coating is single-sided, the coated surface faces the cathode (i.e., the positive electrode sheet).
[0328] Test Method
[0329] 1. Volume average particle size test
[0330] Reference standard GB / T 19077-2016 / ISO 13320:2009 particle size distribution laser diffraction method. Use a laser particle size analyzer (Malvern 3000, MasterSizer 3000) for testing, and use a helium-neon red light source as the main light source. Take a clean small beaker and add 1g of the sample to be tested, add a drop of surfactant to promote sample dispersion, add 20ml of deionized water (the sample concentration ensures that the shading degree is 8-12%), and ultrasonicate at 53KHz / 120W for 5 minutes to ensure that the sample is completely dispersed. Turn on the laser particle size analyzer, clean the optical path system, and automatically test the background. Stir the ultrasonicated test solution to make it evenly dispersed, put it into the sample cell as required, and start measuring the particle size. The measurement results can be read from the instrument.
[0331] 2. Glass transition temperature
[0332] The measurement can be performed by methods commonly used in the art, for example, differential scanning calorimetry according to GB / T 19466.2, with a heating rate of 10°C / min and an air atmosphere.
[0333] 3. Grafting rate test of plasticizer in pressure sensitive adhesive
[0334] It can be detected by infrared testing method, specifically: the organic polymer, plasticizer, and pressure sensitive adhesive are tested to obtain their Fourier infrared spectra, and the pressure sensitive adhesive is detected at 1500-1700 cm -1 A peak different from that of the organic polymer and the single plasticizer appears at the position of the graphite core. This peak represents the grafted plasticizer, and the area under the peak represents the amount of the grafted plasticizer. The grafting rate of the plasticizer can be calculated from this (peak area corresponding to the characteristic peak of the grafted plasticizer / peak area of the plasticizer % 100%).
[0335] 4. Evaluation of the adhesive properties of the isolation film
[0336] The testing process is as follows:
[0337] 1. Select the prepared 300 mm long × 100 mm wide separator and the positive and negative electrode sheets prepared above.
[0338] 2. Wrap the top and bottom of the release film with paper, and use a die cutter and punch to cut into 54.2mm×72.5mm samples.
[0339] 3. Stack the punched separator sample and the positive electrode or negative electrode neatly, with the separator facing upward (the coating facing the positive electrode when coating on one side), and place 130mm×130mm Teflon pads on the upper and lower sides. Place the stacked sample in the middle of a 200mm×200mm cardboard and cover it with a 150mm×160mm cardboard.
[0340] 4. Place the folded sample into the press and adjust the pressure. Adjust the air pressure to 350 kg ± 10 kg (the contact area is about 54.2 mm × 72.5 mm, and the actual pressure after conversion is about 0.87 MPa). Set T = 25 ° C and the time to 15 seconds for pressing.
[0341] 5. Use a die cutter and a punch to punch the hot pressed sample into strips of 72.5 mm x 15 mm.
[0342] 6. Fix one side of the electrode to the steel plate with double-sided tape, and adhere the isolation film to the other side. Use double-sided tape to stick a 15mm wide A4 paper strip to the isolation film to complete the test sample production.
[0343] 7. Turn on the high-speed rail tensile testing machine and set the parameters in sequence: adhesion test, speed 50mm / min, and starting clamp spacing 40mm.
[0344] 8. Place the test sample between the clamps, fix the end of the steel plate to the lower clamp, and fix the A4 paper to the upper clamp. Clamp the upper and lower clamps with the clamps respectively.
[0345] 9. Click the stretching interface on your computer desktop, reset the force and displacement settings, and then click "Start" to pre-stretch approximately 5mm. After pre-stretching, reset the force and displacement settings again and begin the test. During the test, hold the steel plate holding the electrode in place while the tensile testing machine pulls the A4 paper strip upward to separate the separator from the electrode. After the test is complete, export and save the complete data.
[0346] 10. Each group of test samples should be measured on at least 5 samples. If the adhesion test curves of the 5 test samples have good repeatability, then proceed to the next group of tests. Otherwise, it is necessary to test again until the repeatability of the 5 test samples is good.
[0347] 11. After the test is completed, draw a bonding strength (N / m)-displacement curve, take the average value of the 100th to 300th data points as the bonding force, and record the measured bonding force as F0.
[0348] 12. Repeat steps 1 to 11, except that in step 4, the pressure is changed to 850 kg ± 10 kg (equivalent to approximately 2.24 MPa after conversion) and the temperature T is changed to 25°C. The resulting bonding force is recorded as F1.
[0349] 13. Repeat steps 1 to 11, except that in step 4, the pressure is changed to 850 kg ± 10 kg (equivalent to approximately 2.24 MPa after conversion) and the temperature is changed to 95°C. The resulting bonding force is recorded as F2.
[0350] 5. Evaluation of the resistance performance of the isolation film
[0351] The testing process is as follows:
[0352] (1) Preparation of isolation film: Cut each isolation film to be tested into samples of the same size (45.3mm*33.7mm), bake the samples at 60℃ for at least 4h, and then quickly transfer them to a Class 100 clean glove box at 25℃ for later use;
[0353] (2) Preparation of Symmetrical Battery Confinement Pocket Bag (Symmetrical Battery Confinement Aluminum-Plastic Bag (Aluminum-Plastic Bag is a common commodity made of polypropylene and aluminum foil for soft-pack batteries)): A blank symmetrical battery is assembled using Cu Foil against Cu Foil (copper foil against copper foil) as the current collector. The confinement of the pocket bag is achieved by punching a hole in the middle of the green glue. The pocket bag needs to be baked at 60°C for at least 4 hours before use, and then quickly transferred to a 25°C Class 100 clean glove box as described in (1) above for standby use;
[0354] (3) Assembly of symmetrical batteries: Using the negative electrode as the electrode, five groups of symmetrical battery samples with different numbers of isolation membrane layers (1, 2, 3, 4, and 5) were assembled in situ in the glove box described in (1) above, with five replicates for each group. The pocket bag was sealed on the side using a simple packaging machine, and the liquid (300 μL) (electrolyte, with the same composition as the battery electrolyte) was injected with a pipette, and the bottom was sealed.
[0355] (4) Fixturing the assembled symmetrical battery: Place the assembled symmetrical battery in the glove box as described in (1) above overnight to allow the electrolyte to fully infiltrate the isolation membrane; the next day, place the metal fixture, and control the fixture pressure at 0.7 MPa;
[0356] (5) Measure electrochemical impedance spectroscopy (EIS):
[0357] Before the measurement, symmetrical batteries with different numbers of separator layers were placed in a high and low temperature box at 25°C for half an hour, and the EIS at the set temperature (25°C) was measured (if the temperature is low (e.g., -25°C to 0°C), the constant temperature time can be extended accordingly, such as about two hours);
[0358] (6) A French Bio-Logic VMP3 electrochemical workstation was used, with a voltage of <5 V, a current of <400 mA, and a current accuracy of 0.1%*100 μA. The EIS measurement conditions were set to a voltage frequency of 1 MHz to 1 kHz, a perturbation voltage of 5 MV, and a clamp pressure of 0.7 MPa.
[0359] (7) Make a scatter plot of the real part of the EIS data against the negative imaginary part. At the same time, plot the data of parallel samples with different and same numbers of layers on one graph. The EIS graph obtained in this way can be used as a comparison for the original EIS data.
[0360] (8) Eliminate the points outside the first quadrant in the EIS graph obtained in (7) above to obtain a new EIS graph. Perform a linear fit on the scattered points in the first quadrant in the new EIS graph to obtain a correlation equation. Let y = 0, and the x value can be obtained, which is the resistance value of the required isolation membrane in the electrolyte. Similarly, the measured EIS data can be linearly fitted to obtain the resistance values between parallel samples with different numbers of layers. Take five parallel samples with different resistance values and record them as R.
[0361] 6. Performance evaluation of secondary batteries
[0362] Cyclic performance test:
[0363] Five secondary batteries were taken from each group of the prepared batteries, and the secondary batteries were repeatedly charged and discharged through the following steps, and the cycle capacity retention rate of the secondary batteries at 25° C. or 45° C. was calculated.
[0364] In an environment of 25°C, perform the first charge and discharge. Perform constant current and constant voltage charging at a charging current of 0.7C (i.e., the current value that completely discharges the theoretical capacity within 2 hours) until the upper limit voltage reaches 4.4V. Then, perform constant current discharge at a discharge current of 0.5C until the final voltage reaches 3V. Record the discharge capacity of the first cycle. Then, perform 1000 charge and discharge cycles, and record the discharge capacity of the 1000th cycle. Cycle capacity retention = (discharge capacity of the 1000th cycle / discharge capacity of the first cycle) × 100%.
[0365] In an environment of 45°C, perform the first charge and discharge. Perform constant current and constant voltage charging at a charging current of 0.7C (i.e., the current value that completely discharges the theoretical capacity within 2 hours) until the upper limit voltage reaches 4.4V. Then, perform constant current discharge at a discharge current of 0.5C until the final voltage reaches 3V. Record the discharge capacity of the first cycle. Then, perform 1000 charge and discharge cycles, and record the discharge capacity of the 1000th cycle. Cycle capacity retention = (discharge capacity of the 1000th cycle / discharge capacity of the first cycle) × 100%.
[0366] Example 2-3
[0367] Except for the difference in the ratio of (Dv90-Dv10) / Dv50 of the first organic particles in the isolation film coating, the rest is the same as in Example 1. Specifically:
[0368] The ratio (Dv90-Dv10) / Dv50 of the first organic particles of the isolation film prepared in Example 2 is 2.
[0369] The ratio (Dv90-Dv10) / Dv50 of the first organic particles of the isolation film prepared in Example 3 was 2.5.
[0370] Comparative Example 1
[0371] The above is the same as Example 1 except that the (Dv90-Dv10) / Dv50 of the first organic particles in the isolation film coating is 3.5.
[0372] Examples 4-8
[0373] Except for the first organic particles used having different glass transition temperatures, the rest is the same as Example 1. Specifically, the glass transition temperatures of the first organic particles used in Examples 4-8 are 20°C, 30°C, 40°C, 80°C and 100°C, respectively.
[0374] Comparative Examples 2-3
[0375] The process is the same as that of Example 1 except that first organic particles P5 and P11 having glass transition temperatures of 10° C. and 110° C., respectively, are used.
[0376] Examples 9-13
[0377] Except for the isolation film coating, the surface density ρ / R is 0.52 g·m -2 Ω -1 , 0.65g·m -2 Ω -1 , 0.83g·m -2 Ω -1 , 0.96g·m -2 Ω -1 and 0.98 g·m -2 Ω -1 Other than that, the rest is the same as Example 1.
[0378] Comparative Examples 4-6
[0379] Except for the isolation film coating, the surface density ρ / R is 0.26 g·m -2 Ω -1 , 0.29g·m -2 Ω -1 and 0.41 g·m -2 Ω-1 Other than that, the rest is the same as Example 1.
[0380] Examples 14-15
[0381] Except that the first organic particles used are P12 and P13 respectively, the rest are the same as those in Example 1.
[0382] Example 16
[0383] Preparation of isolation membrane
[0384] 1) A polyethylene microporous membrane (purchased from Shanghai Enjie Co., Ltd.) with a thickness of approximately 9 μm, a pore size of approximately 50 nm, and a porosity of approximately 38% was used as the separator substrate;
[0385] 2) adding 21 kg of first organic particles P1 to 140 kg of deionized water and mixing them uniformly to form a first polymer solution;
[0386] 3) adding 23.5 kg of an aqueous emulsion of a pressure-sensitive adhesive (having a glass transition temperature of approximately 10° C. and a volume average particle size Dv50 of approximately 1.1 μm, comprising an organic polymer and a plasticizer in a mass ratio of 5:1 (wherein approximately 8 wt % of the plasticizer is grafted onto the organic polymer relative to the weight of the plasticizer, wherein the organic polymer is a copolymer of 30 wt % isobutyl acrylate, 25 wt % isooctyl acrylate, 5 wt % 2-hydroxypropyl methacrylate, 15 wt % styrene, 22 wt % acrylonitrile, and 3 wt % polyvinyl alcohol, and the plasticizer is glycerol) to the first polymer solution obtained in step 2) and mixing uniformly to obtain a second polymer solution;
[0387] 4) adding an appropriate amount of second organic particles (polyvinylidene fluoride, weight-average molecular weight 500,000 g / mol) to the second polymer solution obtained in step 3) such that the mass ratio of the first organic particles to the second organic particles on a dry weight basis is 90:10, and mixing them uniformly to obtain a third polymer solution, wherein the mass ratio of all organic particles (including the first organic particles and the second organic particles on a dry weight basis at a mass ratio of 90:10) to the pressure-sensitive adhesive on a dry weight basis is 85:15;
[0388] 5) The third polymer solution obtained in step 4) is used as an aqueous coating slurry and is applied to one surface of the isolation membrane substrate by spin spraying. After drying, the isolation membrane is prepared. The prepared isolation membrane includes an isolation membrane substrate and a coating applied on one surface of the isolation membrane substrate. The coating has a thickness of about 3 μm and includes organic particles (including first organic particles and second organic particles in a dry weight ratio of 90:10) and a pressure-sensitive adhesive in a mass ratio of 85:15 based on dry weight. The pressure-sensitive adhesive includes an organic polymer and a plasticizer in a mass ratio of 5:1 (wherein about 8 wt% of the plasticizer is grafted onto the organic polymer relative to the weight of the plasticizer). The coating surface density of the coating is 0.97 g / m 2 As shown in FIG6 , the morphology of the coating layer of the isolation film prepared in this embodiment is shown.
[0389] Examples 17-19
[0390] The same as Example 16 except that the mass ratios of the first organic particles to the second organic particles in the coating on a dry weight basis are 70:30, 50:50 and 40:60 respectively.
[0391] Comparative Example 7
[0392] Except that the first organic particles are not used, the rest is the same as Example 16.
[0393] The compositions of the first organic particles used in Examples and Comparative Examples are shown in Table 1 below.
[0394] The adhesion performance and resistance of the separators prepared in Examples 1-19 and Comparative Examples 1-7, as well as the cycle performance of the secondary batteries prepared using the separators, were evaluated. The results are shown in Table 2 below.
[0395]
[0396]
[0397]
[0398] It can be seen from the results in Tables 1 and 2 above that the use of a pressure-sensitive adhesive prepared from an organic polymer and a plasticizer, combined with organic particles, in the preparation of the isolation membrane can effectively give the isolation membrane high adhesion performance and ion conductivity at room temperature. Specifically, at room temperature, the resistance of the prepared isolation membranes is below 1.89Ω. At room temperature and under the action of ≥2MPa, the adhesion to the positive electrode is above 0.15N / m, especially above 0.4N / m, while under the action of ≤1MPa, the adhesion to the electrode is below 0.08N / m. Therefore, the prepared isolation membrane can avoid excessive adhesion between the layers of the isolation membrane during winding and storage, and when the isolation membrane is used to prepare a battery cell, the electrode and the isolation membrane can be tightly fitted at room temperature. On the one hand, this can avoid the misalignment between the electrode and the isolation membrane, which can cause the battery cell to be scrapped, affect the battery cell performance and create safety risks. On the other hand, it can omit the tunnel furnace and the second composite process in the traditional battery cell production process, thereby saving production space and production time, reducing energy consumption, significantly improving the production capacity of battery cell production, and at the same time improving the battery cell shaping performance, safety performance and dynamic performance. In addition, the isolation membrane of the present application has a better matching relationship between the adhesion force F1 and F2 at room temperature and high temperature.
[0399] Examples 20-21
[0400] Except for the difference in the mass ratio of the organic particles (including the first organic particles and the second organic particles) and the pressure-sensitive adhesive in the coating, and the mass ratio of the first organic particles to the second organic particles on a dry weight basis, the rest is the same as Example 16. Specifically:
[0401] The dry weight ratio of the organic particles to the pressure-sensitive adhesive in the coating layer of the isolation film prepared in Example 20 is 85:15, wherein the dry weight ratio of the first organic particles to the second organic particles in the organic particles is 75:10.
[0402] The mass ratio of organic particles to pressure-sensitive adhesive in the pressure-sensitive coating of the isolation film prepared in Example 21 is 90:10 on a dry weight basis, wherein the mass ratio of first organic particles to second organic particles in the organic particles is 65:25 on a dry weight basis.
[0403] The experimental results of Examples 20-21 are shown in Table 3.
[0404] Table 3 Experimental conditions and experimental results of Examples 20-21
[0405]
[0406] As shown in Table 3, by adjusting the mass ratio of the first organic particles, the second organic particles, and the pressure-sensitive adhesive, the resistance of the separator can be further reduced while avoiding significant degradation of the cycle performance of the secondary battery.
[0407] Examples 22-24
[0408] Except for the different grafting ratio of the plasticizer in the pressure-sensitive adhesive, the rest is the same as Example 1. Specifically:
[0409] The graft ratio of the plasticizer in the pressure-sensitive adhesive used in Example 22 was 5 wt %.
[0410] The graft ratio of the plasticizer in the pressure-sensitive adhesive used in Example 23 was 3 wt %.
[0411] The grafting rate of the plasticizer in the pressure-sensitive adhesive used in Example 24 is 0 wt %, that is, the plasticizer is not grafted.
[0412] The experimental results of Examples 22-24 are shown in Table 4.
[0413] Table 4 Experimental conditions and results of Examples 1 and 22-24
[0414]
[0415] As can be seen from Table 4, by adjusting the grafting rate of the plasticizer, the resistance of the separator can be further reduced, and the bonding performance of the separator and the cycle performance of the corresponding battery can be improved.
[0416] Examples 25-29
[0417] Except for the different particle size of the first organic particles and the different thickness of the coating, the rest is the same as Example 1. Specifically:
[0418] The first organic particles used in Example 25 had a Dv50 particle size of about 3 μm, and a coating thickness of about 0.8 μm.
[0419] The first organic particles used in Example 26 had a Dv50 particle size of about 5 μm, and the coating had a thickness of about 2 μm.
[0420] The first organic particles used in Example 27 had a Dv50 particle size of about 20 μm, and the coating had a thickness of about 15 μm.
[0421] The first organic particles used in Example 28 had a Dv50 particle size of about 30 μm, and the coating had a thickness of about 20 μm.
[0422] The first organic particles used in Example 29 had a Dv50 particle size of about 36 μm, and the coating had a thickness of about 22 μm.
[0423] Examples 30-36
[0424] Except for the different particle size of the pressure-sensitive adhesive, the rest is the same as Example 1. Specifically:
[0425] The pressure-sensitive adhesive used in Example 30 had a Dv50 particle size of approximately 0.3 μm.
[0426] The pressure-sensitive adhesive used in Example 31 had a Dv50 particle size of approximately 0.5 μm.
[0427] The pressure-sensitive adhesive used in Example 32 had a Dv50 particle size of approximately 0.8 μm.
[0428] The pressure-sensitive adhesive used in Example 33 had a Dv50 particle size of approximately 1.0 μm.
[0429] The pressure-sensitive adhesive used in Example 34 had a Dv50 particle size of approximately 2.0 μm.
[0430] The pressure-sensitive adhesive used in Example 35 had a Dv50 particle size of approximately 3.0 μm.
[0431] The pressure-sensitive adhesive used in Example 36 had a Dv50 particle size of approximately 3.5 μm.
[0432] Examples 37-40
[0433] Except for the different particle sizes of the second organic particles used and the different thicknesses of the prepared coatings, the rest is the same as in Example 20. Specifically:
[0434] The second organic particles used in Example 37 have a Dv50 particle size of about 2 μm, and a coating thickness of about 3 μm.
[0435] The second organic particles used in Example 38 had a Dv50 particle size of about 8 μm, and a coating thickness of about 4 μm.
[0436] The second organic particles used in Example 39 had a Dv50 particle size of approximately 10 μm, and a coating thickness of approximately 6 μm.
[0437] The second organic particles used in Example 40 have a Dv50 particle size of about 12 μm, and a coating thickness of about 10 μm.
[0438] The experimental results of Examples 25-40 are shown in Table 5.
[0439]
[0440] As can be seen from Table 5, by adjusting the Dv50 particle size of the first organic particles, the pressure-sensitive adhesive and the second organic particles in the coating and the thickness of the coating, the resistance of the isolation membrane can be further reduced, and the bonding performance of the isolation membrane and the cycle performance of the corresponding battery can be improved.
[0441] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A separator comprising: matrix; and a coating applied on at least one surface of the substrate, the coating comprising 40-90 wt % of first organic particles, 2-15 wt % of a pressure-sensitive adhesive, and optionally 0-50 wt % of second organic particles; wherein the first organic particles include an organic polymer and an inorganic substance, and the pressure-sensitive adhesive includes an organic polymer and a plasticizer; Optionally, the volume average particle size of the first organic particles satisfies (Dv90-Dv10) / Dv50≤2.5, optionally ≤2, more optionally ≤1.8, and the glass transition temperature of the first organic particles is 20-100° C., optionally 30-80° C.; Optionally, the isolation film meets the requirements of 0.1 g·m -2 Ω -1 ≤ρ / R≤1.0g·m -2 Ω -1 , optional 0.5g·m -2 Ω -1 ≤ρ / R≤0.9g·m -2 Ω -1 , 0.6g·m is more optional -2 Ω -1 ≤ρ / R≤0.8g·m -2 Ω -1 , where ρ represents the surface density of the coating on the substrate, and R represents the resistance of the isolation film at 25°C.
2. The isolation film according to claim 1, wherein the first organic particles satisfy one or more of the following conditions: (1) The volume average particle size Dv50 of the first organic particles is 3-36 μm, optionally 5-20 μm; (2) The glass transition temperature of the first organic particles is 20-100° C., optionally 30-80° C.; (3) The weight average molecular weight of the organic polymer in the first organic particles is 500×10 3 g / mol-1000×10 3 g / mol, optional 800×10 3 g / mol-1000×10 3 g / mol.
3. The isolation film according to any one of claims 1 to 2, wherein the organic polymer in the first organic particles is polymerized from at least the following monomers: a first polymerizable monomer having at least one ester bond, which may be selected from one or more of methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, vinyl acetate, trifluoroethyl methacrylate, glycidyl methacrylate, or trimethylolpropane triacrylate, and may further be selected from one or more of methyl methacrylate, lauryl acrylate, lauryl methacrylate, or trimethylolpropane triacrylate; The second polymer monomer has at least one cyanide bond, which can be selected from one or more of acrylonitrile, methacrylonitrile, and ethacrylonitrile, and more preferably one or more of acrylonitrile and methacrylonitrile; The third polymer monomer has at least one amide bond, and may be one or more of acrylamide, N-hydroxymethyl acrylamide, and N-butoxymethyl acrylamide, and may be one or more of acrylamide and N-hydroxymethyl acrylamide; Optionally, the weight ratio of the first polymer monomer: the second polymer monomer: the third polymer monomer is 1:0-0.8:0.05-0.75, and optionally 1:0.1-0.6:0.1-0.
6.
4. The isolation film according to any one of claims 1 to 3, wherein The content of the organic polymer in the first organic particles is 50-99.9%, optionally 60-99%, more optionally 70-99%, based on the total dry weight of the first organic particles; The content of inorganic matter in the first organic particles is 0.1-50%, optionally 1-40%, more optionally 1-30%, based on the total dry weight of the first organic particles. 5 . The isolation film according to claim 1 , wherein a weight ratio of the organic polymer to the inorganic matter in the first organic particles is 99:1 to 1:1, and optionally 70:30 to 1:
1.
6. The isolation film according to any one of claims 1 to 5, wherein based on the total weight of the organic polymer in the first organic particles, The content of the first polymer monomer is 35-80% by weight, optionally 45-70% by weight; The content of the second polymerizable monomer is 0-30 wt%, optionally 5-25 wt%; and The content of the third polymer monomer is 5-40% by weight, and optionally 8-35% by weight.
7. The separator according to any one of claims 1 to 6, wherein The inorganic matter in the first organic particles is selected from one or more of oxides of silicon, aluminum, calcium, zinc, magnesium, sodium sulfate, sodium benzoate, calcium carbonate and modified materials thereof, and can be selected from one or more of silicon dioxide, silica sol, aluminum oxide, zinc oxide, magnesium oxide, sodium benzoate, and more preferably one or more of fumed silica, silicon powder, aluminum oxide, and sodium benzoate. 8 . The isolation film according to claim 1 , wherein the surface of the first organic particles is uneven and inorganic oxide clusters with a particle size of 10-200 nm are evenly distributed. 9 . The isolation film according to claim 1 , wherein the mass ratio of the organic polymer to the plasticizer in the pressure-sensitive adhesive is (4-25):1, or optionally (4-11):
1.
10. The isolation film according to any one of claims 1 to 9, wherein the pressure-sensitive adhesive has a core-shell structure, the core and shell of the core-shell structure both comprise an organic polymer and a plasticizer, wherein the mass ratio of the organic polymer to the plasticizer in the core is (3-4):1, optionally (3.2-3.8):1, and the mass ratio of the organic polymer to the plasticizer in the shell structure is (7-9):1, optionally (7.5-8.5):
1.
11. The release film according to any one of claims 1 to 10, wherein in the pressure-sensitive adhesive, a portion of the plasticizer is grafted onto the organic polymer; Optionally, in the pressure sensitive adhesive, at least 5 wt % of the plasticizer, based on the weight of the plasticizer, is grafted onto the organic polymer.
12. The isolation film according to any one of claims 1 to 11, wherein the pressure-sensitive adhesive has a volume average particle size Dv50 of 0.3-3.5 μm, optionally 0.8-2.0 μm; optionally, the pressure-sensitive adhesive has a glass transition temperature of -50°C to 100°C, optionally -45°C to 60°C.
13. The release film according to any one of claims 1 to 12, wherein in the pressure-sensitive adhesive, the organic polymer comprises a copolymer formed by copolymerizing a mixture comprising at least one of the first monomer group, at least one of the second monomer group, at least one of the third monomer group, and at least one of the reactive dispersants: The first monomer group includes acrylic acid, methacrylic acid, methyl methacrylate, tert-butyl methacrylate, isobornyl methacrylate, hydroxymethyl acrylamide, acrylamide, styrene, and acrylonitrile; The second monomer group: including acrylic acid C4-C 22 Alkyl esters such as isobutyl acrylate, isooctyl acrylate, tert-butyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, ethyl methacrylate, isobutyl methacrylate, 2-ethylhexyl methacrylate, n-hexyl methacrylate, cyclohexyl methacrylate, as well as benzyl methacrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, ethyleneureaethyl methacrylate, dicyclopentenylethoxy methacrylate, tetrahydrofuranyl methacrylate, trifluoroethyl methacrylate, dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, propylene methacrylate, dicyclopentenylethoxy methacrylate; The third monomer group includes 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, glycidyl acrylate, glycidyl methacrylate, dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriisopropoxysilane, γ-methacryloxypropyltrimethoxysilane, N-hydroxymethyl acrylamide, N-butoxymethyl acrylamide, diacetone acrylamide (DAAM), ethyl acetoacetate methacrylate (AAEM), divinylbenzene, epoxy resin with an epoxy value of 0.35-0.50, and divinylbenzene; and Reactive dispersants: including polyvinyl alcohol, polypropylene alcohol, polypropylene glycol, polyethylene glycol, and polyvinyl alcohol.
14. The isolation film according to any one of claims 1 to 13, wherein the plasticizer is selected from one or more of the following: glycerol, C4-C 10 Alkyl diether or monoether, glycerol C4-C 10 Carboxylic acid monoester or diester, propylene glycol C4-C 10 Alkyl monoether or glycerol. 15 . The isolation film according to claim 1 , wherein the average thickness of the coating layer is 0.8-22 μm, optionally 2-15 μm.
16. The isolation film according to any one of claims 1 to 15, wherein The second organic particles are polymers of one or more monomers containing the following groups: halogen, phenyl, epoxy, cyano, ester, and amide; Optionally, the second organic particles are selected from at least one of the following: homopolymers or copolymers of fluorine-containing olefinic monomer units, homopolymers or copolymers of olefinic monomer units, homopolymers or copolymers of unsaturated nitrile monomer units, homopolymers or copolymers of alkylene oxide monomer units, dimers, homopolymers or copolymers of monosaccharide monomer units, and modified compounds of the above homopolymers or copolymers; Further optionally, the second organic particles are selected from at least one of the following: polyperfluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polystyrene-co-methyl methacrylate, polystyrene-co-butyl acrylate, styrene-butyl acrylate-isooctyl acrylate, polymethyl methacrylate, polyacrylonitrile, polyvinyl acetate, polyethylene-co-vinyl acetate, polyimide, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose and cyanoethyl sucrose; Further optionally, the second organic particles are selected from at least one of the following: polyvinylidene fluoride-co-hexafluoropropylene, polystyrene-co-butyl acrylate, styrene-butyl acrylate-isooctyl acrylate, polyperfluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-co-trichloroethylene.
17. The isolation film according to any one of claims 1 to 16, wherein the second organic particles satisfy one or more of the following conditions: (1) The volume average particle size Dv50 of the second organic particles is 2-20 μm, and can be 6-15 μm; (2) The melting point of the second organic particles is 130-160° C., and can be optionally 138-150° C.; (3) The weight average molecular weight of the second organic particles is 400×10 3 g / mol-1000×10 3 g / mol, optional 450×10 3 g / mol-650×10 3 g / mol.
18. The isolation film according to any one of claims 1 to 17, wherein the isolation film satisfies one or more of the following conditions: (1) The porosity of the matrix is 10-95%; (2) The pore size of the substrate is 20-60 nm; (3) The thickness of the substrate is 3-12 μm, optionally 5-9 μm; (4) The substrate is a film or nonwoven fabric selected from one or more of the following: polyethylene, polypropylene, polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyaryletherketone, polyetherimide, polyamideimide, polybenzimidazole, polyethersulfone, polyphenylene oxide, cycloolefin copolymer, polyphenylene sulfide and polyethylene naphthalene.
19. The isolation film according to any one of claims 1 to 18, wherein in the isolation film, The mass ratio of the first organic particles to the second organic particles is 10-100:0-90, and may be 20-90:0-60; Optionally, the ratio of the sum of the mass of the first organic particles and the second organic particles to the mass of the pressure-sensitive adhesive is 20-92:8-20, or optionally 60-90:10-15.
20. The method for preparing the isolation film according to any one of claims 1 to 19, comprising the following steps: S1) adding first organic particles and a dispersant to a solvent to form a first polymer solution; S2) adding a pressure-sensitive adhesive to the first polymer solution obtained in step S1) and mixing thoroughly to form a second polymer solution; S3) optionally, adding second organic particles to the second polymer solution obtained in step S2) and mixing thoroughly to form a third polymer solution; and S4) applying the second polymer solution obtained in step S2) or the third polymer solution obtained in step S3) onto at least one surface of the substrate, and drying to obtain a separator; The isolation film comprises a substrate and a coating coated on at least one surface of the substrate, wherein the coating comprises 40-90 wt% of first organic particles, 2-15 wt% of a pressure-sensitive adhesive, and optionally 0-50 wt% of second organic particles; wherein the first organic particles comprise an organic polymer and an inorganic substance, and the pressure-sensitive adhesive comprises an organic polymer and a plasticizer; optionally, the volume average particle size of the first organic particles satisfies (Dv90-Dv10) / Dv50≤2.5, optionally ≤2, more optionally ≤1.8, and the glass transition temperature of the first organic particles is 20-100°C, optionally 30-80°C; optionally, the isolation film satisfies 0.1 g·m -2 Ω -1 ≤ρ / R≤1.0g·m -2 Ω -1 , optional 0.5g·m -2 Ω -1 ≤ρ / R≤0.9g·m -2 Ω -1 , 0.6g·m is more optional -2 Ω -1 ≤ρ / R≤0.8g·m -2 Ω -1 , where ρ represents the surface density of the coating on the substrate, and R represents the resistance of the isolation film at 25°C.
21. A secondary battery comprising a positive electrode sheet, a negative electrode sheet, a separator located between the positive electrode sheet and the negative electrode sheet, and an electrolyte, wherein the separator is the separator according to any one of claims 1 to 19 or the separator prepared by the method according to claim 20.
22. The secondary battery according to claim 21, wherein The bonding force between the positive electrode sheet and the isolation membrane of the secondary battery satisfies 1.2≤F2 / F1≤4, and can optionally be 1.5≤F2 / F1≤3.8, where F1 represents the bonding force between the positive electrode sheet and the isolation membrane at 25°C and ≥2MPa, and F2 represents the bonding force between the positive electrode sheet and the isolation membrane at 95°C and ≥2MPa. 23 . A battery module comprising the secondary battery according to claim 21 . 24 . A battery pack comprising at least one of the secondary battery according to claim 21 or 22 or the battery module according to claim 23 . 25 . An electrical device comprising at least one of the secondary battery according to claim 21 or 22 , the battery module according to claim 23 , or the battery pack according to claim 24 .